Semiconductor nanoparticles, method of manufacturing the same, electroluminescent device including the same,
By using semiconductor nanoparticles with zinc, selenium and sulfur as the main components, combined with the ratio and retention time differences of specific organic ligands, nanoparticles with improved electroluminescent properties and longer life are prepared, which solves the problems of insufficient electroluminescent properties and short life in the prior art, and improves the performance of electroluminescent devices.
Patent Information
- Application Number
- CN202510128867.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-02
- Filing Date
- 2025-02-05
- Publication Date
- 2025-08-05
AI Technical Summary
The existing semiconductor nanoparticles have problems such as insufficient electroluminescent properties and short device life in electroluminescent devices.
Semiconductor nanoparticles with zinc, selenium and sulfur as the main components, combined with a variety of organic ligands, control the ligand ratio and retention time differences through gas chromatography to prepare nanoparticles with improved electroluminescent properties and longer life, and are used in electroluminescent devices.
The improvement of semiconductor nanoparticles in electroluminescent devices and the extension of device life are achieved, and the optical performance and stability of the device are improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority and all benefits arising therefrom based on Korean Patent Application No. 10-2024-0016847, filed on February 2, 2024 with the Korean Intellectual Property Office, the content of which is incorporated herein by reference in its entirety. Technical field
[0003] The present disclosure relates to semiconductor nanoparticles, methods of manufacturing semiconductor nanoparticles, and devices (including electroluminescent devices and display devices) including semiconductor nanoparticles. Background art
[0004] Semiconductor nanoparticles (e.g., semiconductor nanocrystal particles) can emit light. For example, quantum dots including semiconductor nanocrystals can exhibit quantum confinement effects and exhibit luminescent properties. For example, when electrons excited by light excitation or by applying a voltage undergo transitions from the conduction band to the valence band, light emission of semiconductor nanoparticles can occur. Semiconductor nanoparticles can be configured to emit light in a desired wavelength region by controlling the size, composition, or a combination thereof.
[0005] Nanoparticles can be used in light-emitting devices (e.g., electroluminescent devices) including nanoparticles and display devices. Summary of the invention
[0006] Embodiments provide semiconductor nanoparticles that can exhibit improved properties (e.g., electroluminescent properties and longer device lifetimes).
[0007] Embodiments relate to methods for manufacturing the above-described semiconductor nanoparticles.
[0008] Embodiments provide light-emitting devices, e.g., capable of emitting light by applying a voltage to semiconductor nanoparticles (e.g., quantum dots).
[0009] Embodiments provide display devices (e.g., quantum dot light-emitting diode (“QD-LED”) displays) including nanoparticles as a light-emitting material in blue pixels, red pixels, green pixels, or a combination thereof.
[0010] According to an embodiment, the semiconductor nanoparticles comprise: zinc, selenium, and sulfur, and wherein the semiconductor nanoparticles do not comprise cadmium; wherein the semiconductor nanoparticles comprise a first semiconductor nanocrystal and a semiconductor nanocrystal shell comprising zinc and sulfur disposed on the first semiconductor nanocrystal; the semiconductor nanoparticles further comprise a plurality of organic ligands (or a ligand system comprising the same), and the plurality of organic ligands comprise a first organic ligand having a carboxylate moiety and a second organic ligand different from the first organic ligand and having a carboxylate moiety; wherein in gas chromatography (GC) analysis, the semiconductor nanoparticles exhibit a first peak attributable to the first organic ligand and a second peak attributable to the second organic ligand, and wherein the area percentage of the first peak relative to the second peak is greater than or equal to about 1%, or greater than or equal to about 3% and less than or equal to about 300%.
[0011] The area percentage of the first peak relative to the second peak can be greater than or equal to about 5% and less than or equal to about 150%.
[0012] The area percentage of the first peak relative to the second peak can be less than or equal to about 99%, or less than or equal to about 80%.
[0013] The area percentage of the first peak relative to the second peak can be greater than or equal to about 70%, greater than or equal to about 95%, or greater than or equal to about 100%.
[0014] The second organic ligand can have a higher molecular weight than the first organic ligand.
[0015] The second organic ligand can have a carbon number greater than or equal to about 15, greater than or equal to about 16, or greater than or equal to about 17.
[0016] The ratio of the retention time (residence time) (in minutes) of the first peak to the retention time (in minutes) of the second peak can be greater than or equal to about 0.1:1, greater than or equal to about 0.5:1, or greater than or equal to about 0.7:1 and less than or equal to about 1:1, or less than or equal to about 0.9:1. The retention time of the second peak can be longer than the retention time of the first peak. The difference in retention time between the second peak and the first peak can be greater than or equal to about 2 minutes, or greater than or equal to about 5 minutes. The difference in retention time between the second peak and the first peak can be less than or equal to about 12 minutes, or less than or equal to about 10 minutes.
[0017] The semiconductor nanoparticles can further comprise a halogen. The halogen can be fluorine, chlorine, bromine, iodine, or a combination thereof. In an embodiment, the halogen can be chlorine.
[0018] In the semiconductor nanoparticles, the molar ratio of halogen to zinc can be greater than or equal to about 0.01:1, greater than or equal to about 0.05:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, or greater than or equal to about 0.2:1. In the semiconductor nanoparticles, the molar ratio of halogen to zinc can be less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.7:1, or less than or equal to about 0.5:1.
[0019] The semiconductor nanoparticles, the first semiconductor nanocrystals, or the semiconductor nanocrystal shells can include II-VI group compounds, III-V group compounds, IV-VI group compounds, group IV elements (elemental substances) or compounds, II-III-VI group compounds, I-III-VI group compounds, I-II-IV-VI group compounds, or combinations thereof.
[0020] The semiconductor nanoparticles or the first semiconductor nanocrystals can include indium phosphide, indium zinc phosphide, zinc selenide, zinc telluride, zinc selenium telluride, indium gallium silver sulfide, indium silver sulfide, or combinations thereof. The semiconductor nanoparticles or the semiconductor nanocrystal shells can include zinc selenide, zinc selenium telluride, zinc selenium sulfide, zinc sulfide, or combinations thereof. The semiconductor nanocrystal shell can include a first shell layer; and a second shell layer disposed on the first shell layer. The first shell layer can include zinc selenide, zinc selenium telluride, zinc selenium sulfide, or combinations thereof. The second shell layer can include zinc selenium sulfide, zinc sulfide, or combinations thereof. The semiconductor nanoparticles may not include lead. The semiconductor nanoparticles may not include copper.
[0021] The semiconductor nanoparticles can be configured to emit a first light.
[0022] The first light can have a red spectrum, a green spectrum, or a blue spectrum. The first light can have a full width at half maximum (FWHM) greater than or equal to about 1 nm and less than or equal to about 55 nanometers (nm).
[0023] The first light can be blue light. The emission peak wavelength of the first light or the blue light can be greater than or equal to about 440 nm and less than or equal to about 480 nm.
[0024] The first light can be green light. The emission peak wavelength of the first light or the green light can be greater than or equal to about 500 nm and less than or equal to about 580 nm.
[0025] The first light can be red light. The emission peak wavelength of the first light or the red light can be greater than or equal to about 600 nm and less than or equal to about 680 nm.
[0026] The organic ligand or ligand system can be bound to or disposed on the surface of the semiconductor nanocrystals.
[0027] The total number of carbon atoms in the organic ligand or ligand system can be greater than or equal to about 20, greater than or equal to about 22, greater than or equal to about 24, greater than or equal to about 28, or greater than or equal to about 29. The total number of carbon atoms can be less than or equal to about 34, less than or equal to about 32, less than or equal to about 30, less than or equal to about 28, or less than or equal to about 27.
[0028] The first organic ligand can have a molecular weight greater than or equal to about 90 grams per mole (g / mol), or greater than or equal to about 100 g / mol and less than or equal to about 260 g / mol, less than or equal to about 230 g / mol, less than or equal to about 210 g / mol, less than or equal to about 205 g / mol, less than or equal to about 200 g / mol, or less than or equal to about 170 g / mol.
[0029] The second organic ligand can have a molecular weight greater than about 200 g / mol, greater than or equal to about 225 g / mol, greater than or equal to about 250 g / mol, or greater than or equal to about 280 g / mol and less than or equal to about 500 g / mol, or less than or equal to about 250 g / mol.
[0030] The first organic ligand can include a substituted or unsubstituted C6-C12 aromatic hydrocarbon group, a substituted or unsubstituted C3-C12 or C5-C9 or C4-C8 or C6-C7 straight-chain or branched aliphatic hydrocarbon group (e.g., alkyl, alkenyl, or alkynyl), or a combination thereof.
[0031] The first organic ligand can include a hexanoate moiety substituted with a C1-C3 alkyl group, a butyrate moiety substituted with a C1-C3 alkyl group, a valerate moiety substituted with a C1-C3 alkyl group, an octanoate moiety substituted with a C1-C4 alkyl group, or a combination thereof. The first organic ligand can include a hexanoate group, a methylbutyrate group, a butyloctanoate group, or a combination thereof.
[0032] The second organic ligand can include a C13-C25, C14-C23, C15-C22, C16-C21, C17-C20, or C18-C19 straight-chain or branched aliphatic hydrocarbon group (e.g., alkyl, alkenyl, or alkynyl). The second organic ligand can include an aliphatic hydrocarbon group having 17 or more carbons.
[0033] The second organic ligand can include at least one or at least two carbon-carbon double bonds, such as as a terminal group or within the aliphatic hydrocarbon group chain.
[0034] The first organic ligand can include a branched alkyl group, and the second organic ligand can include a straight-chain alkenyl group.
[0035] The area percentage of the first peak relative to the second peak can be greater than or equal to about 10%, greater than or equal to about 30%, or greater than or equal to about 40%. The area percentage of the first peak relative to the second peak can be less than or equal to about 90%, less than or equal to about 80%, or less than or equal to about 75%.
[0036] The semiconductor nanoparticles may substantially not show a peak attributable to thiol in gas chromatography. The area ratio of the peak attributable to thiol in gas chromatography relative to the second peak can be less than or equal to about 10%, less than or equal to about 5%, less than or equal to about 2%, or less than or equal to about 1%.
[0037] The semiconductor nanoparticles can have a particle size or average particle size (hereinafter simply referred to as "particle size") greater than or equal to about 8 nm, greater than or equal to about 10 nm, or greater than or equal to about 12 nm and less than or equal to about 50 nm, or less than or equal to about 45 nm.
[0038] In thermogravimetric analysis, the semiconductor nanoparticles can have a weight loss (e.g., organic content) in the range of 200 °C to 550 °C as follows: less than or equal to about 13%, less than or equal to about 11.5%, less than or equal to about 11%, or less than or equal to about 8% of the total weight of the semiconductor nanoparticles. In thermogravimetric analysis, the semiconductor nanoparticles can have a weight loss in the range of 200 °C to 550 °C greater than or equal to about 3% of the total weight of the semiconductor nanoparticles.
[0039] In thermogravimetric analysis, the semiconductor nanoparticles can exhibit a residual content greater than or equal to about 550 °C of greater than or equal to about 82%, greater than or equal to about 87%, greater than or equal to about 88%, or greater than or equal to about 89% and less than or equal to about 99%, less than or equal to about 93%, or less than or equal to about 91% of the total weight of the semiconductor nanoparticles.
[0040] In dynamic light scattering analysis (DLS), the semiconductor nanoparticles can exhibit a DLS particle diameter less than about 300 nm. The DLS particle diameter can be less than or equal to about 200 nm, less than or equal to about 100 nm, or less than or equal to about 50 nm. The DLS particle diameter can be greater than or equal to about 10 nm, or greater than or equal to about 15 nm.
[0041] [[ID=ID=18]]In time-resolved photoluminescence spectroscopy, the semiconductor nanoparticles can have an average lifetime (or average decay time) greater than or equal to about 20 nanoseconds (ns), greater than or equal to about 30 ns, greater than or equal to about 40 ns, or greater than or equal to about 50 ns.
[0042] In time-resolved photoluminescence spectroscopy, the semiconductor nanoparticles can have an average lifetime (or average decay time) of less than or equal to about 500 ns, less than or equal to about 300 ns, less than or equal to about 100 ns, or less than or equal to about 80 ns.
[0043] In an embodiment, a method for manufacturing semiconductor nanoparticles includes:
[0044] contacting (e.g., reacting) a zinc precursor and a sulfur precursor in a reaction medium comprising an organic solvent and optionally an organic ligand, in the presence of particles comprising a first semiconductor nanocrystal and optionally a second semiconductor nanocrystal; and
[0045] adding a metal halide to the reaction medium,
[0046] wherein the zinc precursor includes a first zinc precursor comprising a first organic ligand and a zinc ion, and a second zinc precursor comprising a second organic ligand and a zinc ion.
[0047] Details of the first semiconductor nanocrystal, the first organic ligand, and the second organic ligand are as described herein.
[0048] In an embodiment of the method, the first semiconductor nanocrystal may or may not include zinc, selenium, or a combination thereof. In an embodiment of the method, if present, the second semiconductor nanocrystal may include zinc and selenium.
[0049] In an embodiment of the method, the first zinc precursor may first contact the sulfur precursor, and then the second zinc precursor contacts the sulfur precursor. In an embodiment of the method, the second zinc precursor may first contact the sulfur precursor, and then the first zinc precursor contacts the sulfur precursor.
[0050] In an embodiment of the method, the metal halide may be added after the first zinc precursor or the second zinc precursor contacts the sulfur precursor.
[0051] In an embodiment of the method, the first zinc precursor may first contact the sulfur precursor, then the second zinc precursor contacts the sulfur precursor, and the second zinc precursor may be added and mixed into the reaction medium simultaneously with or after the addition of the metal halide.
[0052] In an embodiment of the method, the second zinc precursor may first contact the sulfur precursor, then the first zinc precursor contacts the sulfur precursor, and the first zinc precursor may be added and mixed into the reaction medium simultaneously with or after the addition of the metal halide.
[0053] In an embodiment of the method, based on 1 mole of the first zinc precursor, the amount of the second zinc precursor can be greater than or equal to about 0.01 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.5 mole, greater than or equal to about 1 mole, greater than or equal to about 5 moles, greater than or equal to about 10 moles, greater than or equal to about 50 moles, or greater than or equal to about 100 moles.
[0054] In an embodiment of the method, based on 1 mole of the first zinc precursor, the amount of the second zinc precursor can be less than or equal to about 100 moles, less than or equal to about 70 moles, less than or equal to about 40 moles, less than or equal to about 10 moles, less than or equal to about 3 moles, less than or equal to about 1 mole, less than or equal to about 0.4 mole, less than or equal to about 0.2 mole, less than or equal to about 0.06 mole, or less than or equal to about 0.03 mole.
[0055] In an embodiment of the method, based on 1 mole of the zinc precursor, the amount of the metal halide can be greater than or equal to about 0.01 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.5 mole, greater than or equal to about 1 mole, greater than or equal to about 5 moles, greater than or equal to about 10 moles, greater than or equal to about 50 moles, or greater than or equal to about 100 moles.
[0056] In an embodiment of the method, based on 1 mole of the zinc precursor, the amount of the metal halide can be less than or equal to about 100 moles, less than or equal to about 70 moles, less than or equal to about 40 moles, less than or equal to about 10 moles, less than or equal to about 3 moles, less than or equal to about 1 mole, less than or equal to about 0.4 mole, less than or equal to about 0.2 mole, less than or equal to about 0.06 mole, or less than or equal to about 0.03 mole.
[0057] In an embodiment, the electroluminescent device includes: a first electrode and a second electrode (e.g., spaced apart from each other), and a light-emitting layer disposed between the first electrode and the second electrode, wherein the light-emitting layer includes the semiconductor nanoparticles described above.
[0058] Details of the semiconductor nanoparticles are as described herein.
[0059] The light-emitting layer can be configured to emit a first light when a voltage is applied.
[0060] Details of the first light are as described herein. In an embodiment, the peak wavelength of the first light or the luminescence (e.g., electroluminescence or photoluminescence) of the semiconductor nanoparticles can be greater than or equal to about 440 nm, or greater than or equal to about 460 nm and less than or equal to about 480 nm, or less than or equal to about 470 nm.
[0061] In an embodiment, the peak emission wavelength of the first light or semiconductor nanoparticles (e.g., electroluminescence peak wavelength) can be greater than or equal to about 500 nm, or greater than or equal to about 510 nm and less than or equal to about 580 nm, or less than or equal to about 540 nm. In an embodiment, the peak emission wavelength of the first light or semiconductor nanoparticles can be greater than or equal to about 600 nm, or greater than or equal to about 610 nm and less than or equal to about 680 nm, or less than or equal to about 635 nm.
[0062] The first electrode can be an anode, and the second electrode can be a cathode.
[0063] The electroluminescent device can further include a charge assisting layer between the light emitting layer and the first electrode, between the light emitting layer and the second electrode, or both.
[0064] The electroluminescent device can further include a hole assisting layer between the light emitting layer and the first electrode. The electroluminescent device can further include an electron assisting layer between the light emitting layer and the second electrode.
[0065] The charge assisting layer can include a hole assisting layer containing an organic compound, an electron assisting layer containing metal oxide nanoparticles, or a combination thereof.
[0066] The electroluminescent device can have a maximum brightness greater than or equal to about 80,000 candela per square meter (cd / m²), greater than or equal to about 90,000 cd / m², or greater than or equal to about 100,000 cd / m².
[0067] The electroluminescent device can have a maximum external quantum efficiency greater than or equal to about 9%, greater than or equal to about 10%, or greater than or equal to about 11%.
[0068] The electroluminescent device can have a time (hours, hr) (T90) (e.g., when measured at an initial brightness of 146 nits) greater than or equal to about 1,000 hours until the initial luminance (e.g., brightness) of a given device is reduced to 90%.
[0069] Embodiments relate to an electronic device or a display device including the electroluminescent device.
[0070] The display device or the electronic device can include a virtual reality display device, an augmented reality display device, a mobile terminal device, a monitor, a notebook, a television, a sign, a camera, or an automotive component, etc.
[0071] According to an embodiment, when applied to an electroluminescent device, the semiconductor nanoparticles can exhibit improved optical properties and lifetime characteristics, such as a longer lifetime, and can exhibit dispersion properties suitable for being provided as an ink composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] The above and other advantages and features of the present disclosure will become more apparent by describing in further detail exemplary embodiments of the present disclosure with reference to the accompanying drawings, wherein:
[0073] Figure 1 is a schematic cross-sectional view of an embodiment of a quantum dot light emitting diode (“QD-LED”) device;
[0074] Figure 2 is a schematic cross-sectional view of an embodiment of a QD-LED device; and
[0075] Figure 3 is a schematic cross-sectional view of an embodiment of a QD-LED device.
[0076] Figure 4 is a schematic cross-sectional view of a QD LED device according to an embodiment.
[0077] Figure 5 is a schematic cross-sectional view of a light emitting device (RGB pixel) according to an embodiment.
[0078] Figure 6 is a schematic front view of a display panel according to an embodiment.
[0079] Figure 7 is taken along line IV-IV Figure 6 of the display panel.
[0080] Figure 8 shows the results of gas chromatography analysis illustrating the intensity (count, %) of the semiconductor nanoparticles synthesized in Preparation Examples 1-3 and 6-7 versus the acquisition time (acquisition time) (i.e., retention time, RT) (minutes, min).
[0081] Figure 9 shows the results of gas chromatography analysis illustrating the intensity (count, %) of the semiconductor nanoparticles synthesized in Preparation Example 4 versus the acquisition time (i.e., retention time, RT) (minutes, min).
[0082] Figure 10 shows the results of gas chromatography analysis illustrating the intensity (count, %) of the semiconductor nanoparticles synthesized in Preparation Example 5 versus the acquisition time (i.e., retention time, RT) (minutes, min). Detailed Description
[0083] Advantages and features of the present disclosure, as well as methods for realizing them, will become clear by referring to the following exemplary embodiments and the accompanying drawings. However, the present invention may be embodied in many different forms, and the embodiments should not be construed as limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Like reference numerals always denote like elements.
[0084] To clearly explain the present disclosure, parts irrelevant to the description are omitted, and the same reference numerals are assigned to the same or similar elements throughout the specification. In the drawings, the thicknesses of layers, films, panels, regions, etc. are exaggerated for clarity. Also, in the drawings, the thicknesses of some layers and regions are exaggerated for ease of description. Therefore, the embodiments described herein should not be construed as limited to the specific shapes of the regions shown herein, but include, for example, deviations in shape caused by manufacturing. For example, a region shown or described as flat may typically have rough and / or non-linear features. In addition, the sharp corners shown may be rounded. Thus, the regions shown in the figures are schematic in nature, and their shapes are not intended to show the exact shape of the regions and are not intended to limit the scope of the claims.
[0085] Furthermore, it will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, no intervening elements are present. Additionally, being "on" a reference part means being disposed above or below the reference part, and does not necessarily mean "above".
[0086] Moreover, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another as shown in the figures. It will be understood that, in addition to the orientation shown in the figures, the relative terms are intended to cover different orientations of the device. For example, if the device in one of the figures is flipped, an element described as being on the "lower" side of another element will be oriented on the "upper" side of the other element. Thus, the term "lower" can include both the "lower" and "upper" orientations, depending on the specific orientation of the figure. Similarly, if the device in one of the figures is flipped, an element described as being "under" or "beneath" another element will be oriented as being "above" the other element. Thus, the terms "under" or "beneath" can include both the above and below orientations.
[0087] It will be understood that, although the terms “first,” “second,” “third,” etc. may be used herein to describe various elements, components, regions, layers, and / or sections, these elements, components, regions, layers, and / or sections should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer, or section from another. Thus, a “first element,” “component,” “region,” “layer,” or “section” discussed below may be termed a second element, component, region, layer, or section without departing from the teachings herein.
[0088] The terms used herein are for the purpose of describing particular embodiments only and are not intended to be limiting. As used herein, the singular forms “a,” “an,” and “the” are intended to include the plural forms, including “at least one,” unless the context clearly dictates otherwise. “At least one” is not to be construed as limited to “one.” “Or” means “and / or.”
[0089] As used herein, the term “and / or” includes any and all combinations of one or more of the associated listed items. It will be further understood that when used in this specification, the terms “comprises” or “comprising” indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or groups thereof.
[0090] As used herein, the term “cross section” means the situation where a cross section of a given object is cut, for example, in a substantially vertical direction and observed laterally.
[0091] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. It will be further understood that terms, such as those defined in commonly used (e.g., non-technical) dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of this disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless expressly so defined herein.
[0092] As used herein, the values of work function, conduction band or lowest unoccupied molecular orbital (LUMO) (or valence band or highest occupied molecular orbital (HOMO)) energy levels are expressed as absolute values with respect to the vacuum energy level. Further, when the work function or energy level is referred to as "deep", "high", or "large", the work function or energy level has a large absolute value based on the vacuum energy level of "0 electron volts (eV)", and when the work function or energy level is referred to as "shallow", "low", or "small", the work function or energy level has a small absolute value based on the vacuum energy level of "0 electron volts (eV)". In one aspect, the work function herein refers to the minimum energy required to remove an electron from, for example, a solid metal (e.g., a metal surface) to a vacuum (e.g., just outside the solid surface).
[0093] As used herein, the term "first absorption peak" refers to the main exciton peak that first appears (i.e., appears in the lowest energy region of the UV-Vis absorption spectrum) starting from the longest wavelength region of the ultraviolet-visible (UV-Vis) absorption spectrum, and the term "first absorption peak wavelength" or "wavelength of the first absorption peak" refers to the wavelength at which the first absorption peak reaches its maximum intensity.
[0094] As used herein, the average (value) may be the mean or the median. In an embodiment, the average (value) may be the mean.
[0095] As used herein, the term "peak emission wavelength" is the wavelength at which a given emission spectrum of light reaches its maximum value.
[0096] As used herein, the term "group" may refer to a group of the periodic table.
[0097] As used herein, "Group I" refers to Group IA and Group IB, and examples may include, but are not limited to, Li, Na, K, Rb, and Cs.
[0098] As used herein, "Group II" refers to Group IIA and Group IIB, and examples of Group II metals may be, but are not limited to, Cd, Zn, Hg, and Mg.
[0099] As used herein, "Group III" refers to Group IIIA and Group IIIB, and examples of Group IIIA metals may be, but are not limited to, Al, In, Ga, and Tl, and examples of Group IIIB may be scandium, yttrium, etc., but are not limited to these.
[0100] As used herein, "Group IV" refers to Group IVA and Group IVB, and examples of Group IVA metals may be, but are not limited to, Si, Ge, and Sn, and examples of Group IVB metals may be titanium, zirconium, hafnium, etc., but are not limited to these.
[0101] As used herein, "Group V" includes Group VA and includes nitrogen, phosphorus, arsenic, antimony, and bismuth, but is not limited to these.
[0102] As used herein, "Group VI" includes Group VIA and includes sulfur, selenium, and tellurium, but is not limited thereto.
[0103] As used herein, "metal" includes metalloids such as Si.
[0104] As used herein, the number of carbon atoms in a group or molecule may be referred to as a subscript (e.g., C 6-50 ) or as C6 - C50.
[0105] As used herein, when no other definition is provided, "substituted" means that at least one hydrogen of a compound or group is replaced by a corresponding substituent, and the substituents include C1 - C30 alkyl, C2 - C30 alkenyl, C2 - C30 alkynyl, C6 - C30 aryl, C7 - C30 alkylaryl, C1 - C30 alkoxy, C1 - C30 heteroalkyl, C3 - C30 heteroaryl, C3 - C30 cycloalkyl, C3 - C15 cycloalkenyl, C6 - C30 cycloalkynyl, C2 - C30 heterocycloalkyl, halogen (-F, -Cl, -Br or -I), hydroxy (-OH), nitro (-NO2), cyano (-CN), amino (-NRR', where R and R' are each independently hydrogen or C1 - C6 alkyl), azido (-N3), amidino (-C(=NH)NH2), hydrazino (-NHNH2), hydrazono (=N(NH2)), aldehyde (-C(=O)H), carbamoyl (-C(O)NH2), mercapto (-SH), ester (-C(=O)OR, where R is C1 - C6 alkyl or C6 - C12 aryl), carboxy (-COOH) or its salt (-C(=O)OM, where M is an organic or inorganic cation), sulfonic acid group (-SO3H) or its salt (-SO3M, where M is an organic or inorganic cation), phosphoric acid group (-PO3H2) or its salt (-PO3MH or -PO3M2, where M is an organic or inorganic cation), or a combination thereof.
[0106] As used herein, when no other definition is provided, "hydrocarbon" or "hydrocarbon group" means a compound or group that includes carbon and hydrogen (e.g., alkyl, alkenyl, alkynyl, or aryl). A hydrocarbon group may be a monovalent group formed by removing one or more hydrogen atoms from an alkane, alkene, alkyne, or arene or a group having a valence greater than one. In a hydrocarbon or hydrocarbon group, at least one methylene may be replaced by an oxide (oxygen) moiety, a carbonyl moiety, an ester moiety, -NH-, or a combination thereof. Unless otherwise stated to the contrary, a hydrocarbon or hydrocarbon group (alkyl, alkenyl, alkynyl, or aryl) may have 1 to 60, 2 to 32, 3 to 24, or 4 to 12 carbon atoms.
[0107] As used herein, when no other definition is provided, "alkyl" refers to a straight-chain or branched saturated monovalent hydrocarbon group (such as methyl, ethyl, hexyl, etc.). In embodiments, the alkyl may have 1 to 50 carbon atoms, or 1 to 18 carbon atoms, or 1 to 12 carbon atoms.
[0108] As used herein, when no other definition is provided, "alkenyl" refers to a straight-chain or branched monovalent hydrocarbon group having a carbon-carbon double bond. In embodiments, the alkenyl may have 2 to 50 carbon atoms, or 2 to 18 carbon atoms, or 2 to 12 carbon atoms.
[0109] As used herein, when no other definition is provided, "alkynyl" refers to a straight-chain or branched monovalent hydrocarbon group having a carbon-carbon triple bond. In embodiments, the alkenyl may have 2 to 50 carbon atoms, or 2 to 18 carbon atoms, or 2 to 12 carbon atoms.
[0110] As used herein, when no other definition is provided, "aryl" refers to a group having a carbocyclic aromatic system. When the aryl includes multiple rings, the multiple rings may be fused to each other. Examples include phenyl and naphthyl. In embodiments, the aryl may have 6 to 50 carbon atoms, or 6 to 18 carbon atoms, or 6 to 12 carbon atoms.
[0111] As used herein, when no other definition is provided, "hetero" refers to containing 1 to 3 heteroatoms, such as N, O, P, Si, B, Se, Ge, Te, S, or a combination thereof.
[0112] As used herein, "heteroaryl" refers to an aromatic system having at least one N, O, P, Si, B, Se, Ge, Te, S, or a combination thereof as a ring-forming atom. Examples of heteroaryl include pyridyl, pyrimidinyl, pyrazinyl, pyridazinyl, triazinyl, quinolinyl, and isoquinolinyl. When the heteroaryl includes multiple rings, the multiple rings may be fused to each other. In embodiments, the heteroaryl may have 3 to 50 carbon atoms, or 6 to 18 carbon atoms, or 6 to 12 carbon atoms.
[0113] As used herein, when no other definition is provided, "alkoxy" refers to an alkyl group attached to oxygen (e.g., alkyl-O-), such as methoxy, ethoxy, or sec-butoxy.
[0114] As used herein, the term "cycloalkyl" refers to a monovalent monocyclic saturated hydrocarbon group. Examples thereof include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl. In embodiments, the cycloalkyl may have 3 to 50 carbon atoms, or 3 to 18 carbon atoms, or 3 to 12 carbon atoms.
[0115] As used herein, the term "heterocycloalkyl" refers to a monovalent monocyclic group that includes at least one N, O, P, Si, B, Se, Ge, Te, S, or a combination thereof as a ring-forming atom in addition to carbon atoms as ring-forming atoms. Examples thereof include tetrahydrofuranyl and tetrahydrothienyl. In an embodiment, the heterocycloalkyl may have 2 to 50 carbon atoms, or 2 to 18 carbon atoms, or 2 to 12 carbon atoms.
[0116] As used herein, the term "cycloalkenyl" refers to a monovalent monocyclic hydrocarbon group having at least one carbon-carbon double bond in its ring, wherein the molecular structure as a whole is non-aromatic. Examples thereof include cyclopentenyl, cyclohexenyl, and cycloheptenyl. In an embodiment, the cycloalkenyl may have 3 to 50 carbon atoms, or 3 to 18 carbon atoms, or 3 to 12 carbon atoms.
[0117] As used herein, the term "heterocycloalkenyl" refers to a monovalent monocyclic group that includes at least one N, O, P, Si, B, Se, Ge, Te, S, or a combination thereof as a ring-forming atom and includes at least one double bond in its ring, wherein the molecular structure as a whole is non-aromatic. Examples of heterocycloalkenyl include 2,3-dihydrofuranyl and 2,3-dihydrothienyl. In an embodiment, the heterocycloalkenyl may have 2 to 50 carbon atoms, or 2 to 18 carbon atoms, or 2 to 12 carbon atoms.
[0118] The term "arylalkyl" refers to an alkyl group substituted with an aryl group. An example of arylalkyl is benzyl (i.e., -CH2-phenyl).
[0119] The term "alkylaryl" refers to an aryl group substituted with an alkyl group. An example of alkylaryl is tolyl.
[0120] As used herein, when no other definition is provided, "amine" is a compound represented by NR3, wherein each R is independently hydrogen, a C1-C12 alkyl group, a C7-C20 alkylaryl group, a C7-C20 arylalkyl group, or a C6-C18 aryl group.
[0121] As used herein, the expression "not including cadmium (or other harmful heavy metals)" means that the concentration of cadmium (or other heavy metals considered harmful) may be less than or equal to about 100 parts per million by weight (ppmw), less than or equal to about 50 ppmw, less than or equal to about 10 ppmw, less than or equal to about 1 ppmw, less than or equal to about 0.1 ppmw, less than or equal to about 0.01 ppmw, or zero. In an embodiment, cadmium (or other toxic heavy metals) may be substantially absent, or if present, the amount of cadmium (or other heavy metals) may be less than or equal to the detection limit of a given analytical tool (e.g., an inductively coupled plasma atomic emission spectrometry instrument) or its impurity level.
[0122] Unless otherwise indicated, the numerical ranges recited herein are inclusive. Unless otherwise indicated, the numerical ranges recited herein include any real number within the endpoints of the stated range and include the endpoints. In this specification, numerical endpoints or upper or lower limit values (e.g., recited as “greater than or equal to a value,” “at least a value,” or “less than or equal to a value,” or recited with “from” or “to”) may be used to form a numerical range for a given feature. In other words, the upper and lower endpoints recited for each numerical value may be combined independently to provide a range.
[0123] As used herein, “about” includes the stated value and means within an acceptable deviation range for the specific value as determined by one of ordinary skill in the art in view of the measurements discussed and the error associated with the measurement of the specific quantity (i.e., the limitations of the measurement system). For example, “about” may mean within one or more standard deviations of the stated value, or within ±10%, ±5%, ±3%, or ±1%.
[0124] As used herein, a nanoparticle is a structure having at least one region or characteristic scale with a nanoscale dimension. In embodiments, the scale (or average scale) of the nanostructure is less than or equal to about 500 nanometers (nm), less than or equal to about 300 nm, less than or equal to about 250 nm, less than or equal to about 150 nm, less than or equal to about 100 nm, less than or equal to about 50 nm, or less than or equal to about 30 nm, and may be greater than about 0.1 nm or greater than about 1 nm. In embodiments, the nanoparticle may have any suitable shape. Nanoparticles (e.g., semiconductor nanoparticles or metal oxide nanoparticles) may include nanowires, nanorods, nanotubes, branched nanostructures, nanorhombic dodecahedra, nanotripods, nanobipods, nanodots, multi-legged shapes such as at least two legs, and the like and are not limited thereto. The nanoparticle may be, for example, substantially crystalline, substantially single crystal, polycrystalline, (e.g., at least partially) amorphous (non-crystalline), or a combination thereof.
[0125] In embodiments, semiconductor nanoparticles such as quantum dots may exhibit quantum confinement or exciton confinement. As used herein, the term “quantum dot” or “semiconductor nanostructure” is not limited in its shape unless otherwise defined. The semiconductor nanoparticle or quantum dot may have a size less than the Bohr excitation diameter of the bulk crystalline material having the same composition and may exhibit a quantum confinement effect. The semiconductor nanoparticle or quantum dot may emit light corresponding to its bandgap energy by controlling the size of the nanocrystal that acts as the emission center.
[0126] As used herein, the term "T50" is the time (in hours, hr) it takes for the luminance (e.g., brightness) of a given device to decrease to 50% of the initial luminance (100%) when, for example, the given device is driven starting from a predetermined initial luminance (e.g., 650 nits) during operation.
[0127] As used herein, the term "T90" is the time (hr) it takes for the luminance (e.g., brightness) of a given device to decrease to 90% of the initial luminance (100%) when the given device is driven starting from a predetermined initial luminance (e.g., 650 nits).
[0128] As used herein, the phrase "external quantum efficiency (EQE)" is the ratio of the number of photons emitted from a light-emitting diode (LED) to the number of electrons passing through the device, and can be a measure of how effectively a given device converts electrons into photons and allows the photons to escape. The EQE can be determined by the following equation:
[0129] EQE = (injection efficiency) × ((solid-state) quantum yield) × (extraction efficiency)
[0130] Where the injection efficiency is the proportion of electrons passing through the device that are injected into the active region, the quantum yield is the proportion of all electron-hole recombinations in the active region that are radiative and generate photons, and the extraction efficiency is the proportion of photons generated in the active region that escape from the given device.
[0131] As used herein, the maximum EQE is the maximum value of the EQE.
[0132] As used herein, the maximum brightness is the highest value of the brightness for a given device.
[0133] As used herein, the phrase "quantum efficiency" can be used interchangeably with the phrase quantum yield. In embodiments, the quantum efficiency can be a relative quantum yield or an absolute quantum yield, e.g., which can be easily measured by any suitable (e.g., commercially available) device. The quantum efficiency (or quantum yield) can be measured in solution state or solid state (as a complex). In embodiments, the "quantum yield (or quantum efficiency)" can be the ratio of photons emitted (e.g., by a nanostructure or a group of nanostructures) to photons absorbed. In embodiments, the quantum efficiency can be determined by any suitable method. For example, there are two methods for measuring fluorescence quantum yield or efficiency: an absolute method and a relative method.
[0134] The absolute method directly obtains the quantum yield as follows: by detecting the fluorescence of all samples using an integrating sphere. In the relative method, the fluorescence intensity of a standard sample (e.g., a standard dye) can be compared with that of an unknown sample to calculate the quantum yield of the unknown sample. Coumarin 153, Coumarin 545, Rhodamine 101 inner salt, Anthracene, and Rhodamine 6G can be used as standard dyes, depending on their photoluminescence (PL) wavelength, but are not limited thereto.
[0135] As used herein, the term "dispersion" refers to a dispersion in which the dispersed phase is a solid and the continuous medium includes a liquid or a solid different from the dispersed phase. In an embodiment, the ink composition can be in the form of a dispersion. Herein, the "dispersion" can be a colloidal dispersion in which the dispersed phase has a scale greater than or equal to about 1 nm, such as greater than or equal to about 2 nm, greater than or equal to about 3 nm, or greater than or equal to about 4 nm to several micrometers (μm) or less (e.g., less than or equal to about 2 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 800 nm, less than or equal to about 700 nm, less than or equal to about 600 nm, or less than or equal to about 500 nm).
[0136] The bandgap energy of semiconductor nanoparticles can change with the size and composition of the nanocrystals. For example, as the size of the semiconductor nanoparticles increases, the bandgap energy of the semiconductor nanoparticles can become smaller, such as narrower, and the semiconductor nanoparticles can emit light with an increased wavelength. Semiconductor nanocrystals can be used as luminescent materials in various fields, such as in display devices, energy devices, or bioluminescent devices.
[0137] In a light-emitting layer, quantum dots capable of exhibiting electro-luminescence properties at a practically applicable level may include harmful heavy metals, such as cadmium (Cd), lead, mercury, or a combination thereof. Therefore, it is desirable to provide a light-emitting device or a display device having a light-emitting layer substantially free of harmful heavy metals. In QD-LEDs, satisfactory electro-luminescence properties can be based on cadmium-based (i.e., cadmium-containing) LEDs, and there is room for improvement in QD-LED devices that do not include cadmium or other harmful heavy metals and use environmentally friendly quantum dots and emit, for example, blue light.
[0138] The semiconductor nanoparticles according to an embodiment are environmentally friendly, can emit light of a desired wavelength (e.g., blue light) with improved luminous efficiency, and can exhibit improved stability against the external environment. The electro-luminescence device according to an embodiment includes semiconductor nanoparticles and is a self-emitting light-emitting device configured to emit desired light by applying a voltage with or without a separate light source. The light-emitting device and the display device of the embodiment are desirable from an environmental perspective.
[0139] In an embodiment, the semiconductor nanoparticles may include zinc, selenium, and sulfur. The semiconductor nanoparticles may include a first semiconductor nanocrystal; and a semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal and including zinc and sulfur, and the semiconductor nanoparticles may not include cadmium. The semiconductor nanoparticles may further include a plurality of organic ligands (or a ligand system including them). The plurality of organic ligands may include a first organic ligand having a carboxylate moiety; and a different second organic ligand having a carboxylate moiety. The second organic ligand may have a greater molecular weight or a greater number of carbon atoms than the first organic ligand. In gas chromatography (GC) analysis, the semiconductor nanoparticles may show a first peak attributable to (i.e., corresponding to) the first organic ligand and a second peak attributable to (i.e., corresponding to) the second organic ligand, and the area percentage of the first peak relative to the second peak is greater than or equal to about 0.5%, greater than or equal to about 1%, greater than or equal to about 3% and less than or equal to about 300%, less than or equal to about 150%, less than or equal to about 130%, or less than or equal to about 99%.
[0140] An embodiment relates to an electronic device (electroluminescent device) including the semiconductor nanoparticles (e.g., in a light-emitting layer).
[0141] In an embodiment, the electroluminescent device may include: a first electrode 1 and a second electrode 5 spaced apart from each other (e.g., each electrode has a surface opposite to the other, i.e., each electrode has a surface facing each other); and a light-emitting layer 3 disposed between the first electrode 1 and the second electrode 5. (See Figure 1 .) The light-emitting layer may include semiconductor nanoparticles. The light-emitting layer or the semiconductor nanoparticles may not include cadmium. The first electrode may include an anode, and the second electrode may include a cathode. The first electrode may include a cathode, and the second electrode may include an anode. In an embodiment, the electroluminescent device may further include a hole assisting layer 2 between the light-emitting layer and the first electrode. In an embodiment, the electroluminescent device may further include an electron assisting layer 4 between the light-emitting layer and the second electrode.
[0142] In the electroluminescent device of an embodiment, the first electrode 10 or the second electrode 50 may be disposed on a (transparent) substrate 100. The transparent substrate may be a light extraction surface. (See Figure 2 and 3 ).
[0143] Referring to Figure 2 and Figure 3, in the light-emitting device of the embodiment, the light-emitting layer 30 may be disposed between the first electrode (e.g., anode) 10 and the second electrode (e.g., cathode) 50. The cathode 50 may include an electron injection conductor. The anode 10 may include a hole injection conductor. The work functions of the electron / hole injection conductors included in the cathode and the anode may be appropriately adjusted and are not particularly limited. For example, the cathode may have a small work function and the anode may have a relatively large work function, or vice versa.
[0144] The electron / hole injection conductor may include: a metal-based (e.g., metal-containing) material (e.g., metal, metal compound, alloy, or a combination thereof) (e.g., aluminum, magnesium, tungsten, nickel, cobalt, platinum, palladium, calcium, LiF, etc.); a metal oxide such as indium gallium oxide or indium tin oxide (ITO); or a conductive polymer (e.g., having a relatively high work function) such as polyethylenedioxythiophene, but is not limited thereto.
[0145] The first electrode, the second electrode, or a combination thereof may be a light-transmissive electrode or a transparent electrode. In the embodiment, both the first electrode and the second electrode may be light-transmissive electrodes. The electrodes may be patterned. The first electrode, the second electrode, or a combination thereof may be disposed on a (e.g., insulating) substrate. The substrate may be optically transparent (e.g., may have a light transmittance of greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 85%, or greater than or equal to about 90% and, for example, less than or equal to about 99%, or less than or equal to about 95%). The substrate may include regions for blue pixels, regions for red pixels, regions for green pixels, or a combination thereof. Thin-film transistors may be disposed in each region of the substrate, and one of the source electrode and the drain electrode of the thin-film transistor may be electrically connected to the first electrode or the second electrode.
[0146] The light-transmissive electrode may be disposed on a (e.g., insulating) transparent substrate. The substrate may be a rigid or flexible substrate. The substrate may include a plastic or organic material such as a polymer, an inorganic material such as glass, or a metal.
[0147] The light-transmissive electrode may have a light transmittance of greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, or greater than or equal to about 90%, for example, about 80% to about 100%, about 85% to about 95%, or a combination thereof.
[0148] The light-transmitting electrode can be made of, for example, transparent conductors such as indium tin oxide (ITO) or indium zinc oxide (“IZO”), indium gallium tin oxide, indium tin zinc oxide, titanium nitride, polyaniline, LiF / Mg:Ag, etc., or single-layer or multi-layer metal thin films, but not limited thereto. If one of the first electrode and the second electrode is an opaque electrode, the opaque electrode can be made of an opaque conductor such as aluminum (Al), lithium-aluminum (Li:Al) alloy, magnesium-silver (Mg:Ag) alloy, or lithium fluoride-aluminum (LiF:Al) compound. In the case of an alloy electrode, the ratio between the respective materials can be appropriately adjusted, for example, within the range of about 1:0.1 to about 1:10, about 1:0.2 to about 1:5, about 1:0.3 to about 1:3, or a combination thereof.
[0149] The multi-layer electrode can include, for example, a semi-transparent conductive material such as indium tin oxide, an opaque conductive material such as aluminum (or a reflective electrode material), or a combination thereof. In an embodiment, the electrode (e.g., an anode or a cathode) can have a structure in which an opaque conductive material (or a reflective electrode material layer) is disposed between semi-transparent conductive materials (e.g., a semi-transparent conductive material layer). In an embodiment, the electrode (anode or cathode) can have a structure in which a semi-transparent conductive material (e.g., a semi-transparent conductive material layer) is disposed between opaque conductive materials (or a reflective electrode material).
[0150] When a voltage is applied between the first electrode and the second electrode, the light-emitting layer can emit light upward, downward, or a combination thereof through an electric field, and the light traveling to the reflective electrode can be reflected and emitted in the opposite direction.
[0151] In an embodiment, the light can be emitted toward the cathode. In an embodiment, the light can be emitted toward the anode.
[0152] The thickness of each of the electrodes (the first electrode, the second electrode, or each of the first electrode and the second electrode) is not particularly limited and can be appropriately selected in consideration of device efficiency. For example, the thickness of the electrode can be greater than or equal to about 5 nm, greater than or equal to about 10 nm, greater than or equal to about 20 nm, greater than or equal to about 30 nm, greater than or equal to about 40 nm, or greater than or equal to about 50 nm. For example, the thickness of the electrode can be less than or equal to about 100 micrometers (μm), less than or equal to about 90 μm, less than or equal to about 80 μm, less than or equal to about 70 μm, less than or equal to about 60 μm, less than or equal to about 50 μm, less than or equal to about 40 μm, less than or equal to about 30 μm, less than or equal to about 20 μm, less than or equal to about 10 μm, less than or equal to about 1 μm, less than or equal to about 900 nm, less than or equal to about 500 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, or less than or equal to about 60 nm.
[0153] The method of forming the electrode is not particularly limited and can be appropriately selected according to the material. In an embodiment, the electrode can be formed by vapor deposition, coating, or a combination thereof, but is not limited thereto.
[0154] The light-emitting layer 3 or 30 disposed between the first electrode 1 and the second electrode 5 (e.g., anode 10 and cathode 50) may include semiconductor nanoparticles (e.g., blue light-emitting nanoparticles, red light-emitting nanoparticles, green light-emitting nanoparticles, or a combination thereof). The light-emitting layer may include a single layer of one or more (e.g., 2 or more or 3 or more and 10 or less) nanostructures.
[0155] The light-emitting layer can be patterned. In an embodiment, the patterned light-emitting layer may include a blue light-emitting layer 30B disposed in a blue pixel, a red light-emitting layer 30R disposed in a red pixel, a green light-emitting layer 30G disposed in a green pixel, or a combination thereof. The (e.g., red, green, or blue) light-emitting layers can be optically separated from adjacent light-emitting layers (e.g., by a partition wall). In an embodiment, a partition wall such as a black matrix or a pixel defining layer (PDL) can be disposed between the red light-emitting layer, the green light-emitting layer, and the blue light-emitting layer. (See Figure 4 and Figure 5 .) The red light-emitting layer, the green light-emitting layer, and the blue light-emitting layer can be optically isolated from each other.
[0156] The light-emitting layer or the semiconductor nanoparticles may not include cadmium. The light-emitting layer or the semiconductor nanoparticles may not include lead, mercury, or a combination thereof. The semiconductor nanoparticles may further include or may not include copper, manganese, or a combination thereof.
[0157] The semiconductor nanoparticles included in the light-emitting layer 3 or 30 may include zinc, selenium, and sulfur. Embodiments provide semiconductor nanoparticles or a group thereof.
[0158] In an embodiment, the semiconductor nanoparticles include zinc, selenium, and sulfur. The semiconductor nanoparticles may have a core-shell structure. The semiconductor nanoparticles or the core-shell structure includes a first semiconductor nanocrystal; and a semiconductor nanocrystal shell disposed on the first semiconductor nanocrystal and including zinc and sulfur (e.g., including a third semiconductor nanocrystal).
[0159] The semiconductor nanoparticles or the first semiconductor nanocrystal may include indium phosphide, indium zinc phosphide, zinc selenide, zinc telluride, zinc selenium telluride (e.g., zinc selenotelluride, tellurium (or selenium)-doped zinc selenide (or zinc telluride)), indium gallium silver sulfide, indium silver sulfide, or a combination thereof.
[0160] The semiconductor nanoparticles or semiconductor nanocrystal shells may include zinc selenide, zinc selenotelluride, zinc selenosulfide, zinc sulfide, or a combination thereof. The semiconductor nanocrystal shell may include: a first shell layer (including a second semiconductor nanocrystal); and a second shell layer disposed on the first shell layer and including, for example, a third semiconductor nanocrystal. The first shell layer or the second semiconductor nanocrystal may include zinc selenide, zinc selenotelluride, zinc selenosulfide, or a combination thereof. The second shell layer or the third semiconductor nanocrystal may include zinc selenosulfide, zinc sulfide, or a combination thereof. In an embodiment, the core-shell semiconductor nanoparticles may include a semiconductor nanocrystal shell on a first semiconductor nanocrystal (or a core including the same). Depending on the compositions of the first semiconductor nanocrystal and the semiconductor nanocrystal shell, the semiconductor nanoparticles may have a type-I, type-II, or quasi-type-II band alignment and may be configured to emit light of a desired wavelength when a voltage is applied.
[0161] In an embodiment, the semiconductor nanoparticles, the first semiconductor nanocrystal, or the semiconductor nanocrystal shell (e.g., the second semiconductor nanocrystal or the third semiconductor nanocrystal) may each independently include a II-VI group compound, a III-V group compound, a IV-VI group compound, a group-IV element (elemental) or compound, a II-III-VI group compound, a I-III-VI group compound, a I-II-IV-VI group compound, or a combination thereof.
[0162] The II-VI group compounds may include: binary compounds, such as ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, or a combination thereof; ternary compounds, such as ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, or a combination thereof; quaternary compounds, such as HgZnTeS, HgZnSeS, HgZnSeTe, HgZnSTe, or a combination thereof; or a combination thereof. The II-VI group compounds may further include a group-III metal.
[0163] III-V compounds may include: binary compounds such as GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb or combinations thereof; ternary compounds such as GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb or combinations thereof; quaternary compounds such as GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb or combinations thereof; or combinations thereof. The III-V compounds may further include Group II metals (such as InZnP).
[0164] IV-VI compounds may include: binary compounds such as SnS, SnSe, SnTe, PbS, PbSe, PbTe or combinations thereof; ternary compounds such as SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe or combinations thereof; quaternary compounds such as SnPbSSe, SnPbSeTe, SnPbSTe or combinations thereof; or combinations thereof.
[0165] Examples of I-III-VI compounds may include CuInSe2, CuInS2, CuInGaSe and CuInGaS, but are not limited thereto. Examples of I-III-VI compounds may include: ternary compounds such as AgInS, AgInS2, AgInSe2, AgGaS, AgGaS2, AgGaSe2, CuInS, CuInS2, CuInSe2, CuGaS2, CuGaSe2, CuGaO2, AgGaO2, AgAlO2 or combinations thereof; quaternary compounds such as AgInGaS2, AgInGaSe2; or combinations thereof.
[0166] Examples of I-II-IV-VI compounds may be CuZnSnSe and CuZnSnS, but are not limited thereto.
[0167] Group IV elements (elemental substances) or compounds may include: elemental substances (single elements) such as Si, Ge or combinations thereof; binary compounds such as SiC, SiGe or combinations thereof; or combinations thereof.
[0168] Each element included in a multicomponent compound, such as a binary compound, ternary compound, or quaternary compound, may be present in the particles at a uniform concentration or at a non-uniform concentration. For example, the above chemical formula indicates the types of elements included in the compound, and the ratios between the elements in the compound may be different. For example, the chemical formula "AgInGaS2" may include AgIn x Ga 1- x S2 (where x is a real number greater than 0 and less than 1), but is not limited thereto.
[0169] In an embodiment, the first semiconductor nanocrystal may include metal and non-metal elements, the metal including indium, zinc, or a combination thereof, and the non-metal element including phosphorus, selenium, tellurium, sulfur, or a combination thereof. In an embodiment, the second semiconductor nanocrystal may include metal and non-metal elements, the metal including indium, zinc, or a combination thereof, and the non-metal element including phosphorus, selenium, tellurium, sulfur, or a combination thereof.
[0170] In an embodiment, the first semiconductor nanocrystal may include InP, InZnP, ZnSe, ZnSeS, ZnSeTe, or a combination thereof; the second semiconductor nanocrystal may include ZnSe, ZnSeS, ZnS, ZnTeSe, or a combination thereof. In an embodiment, the shell may include zinc, sulfur, and optionally selenium, for example, in the outermost layer.
[0171] In an embodiment, the semiconductor nanoparticle may emit blue or green light and may include a core and a shell, the core including ZnSeTe, ZnSe, or a combination thereof, and the shell including a zinc chalcogenide (e.g., ZnS, ZnSe, ZnSeS, or a combination thereof). The amount of sulfur in the shell may increase or decrease in the radial direction (from the core towards the surface). For example, the amount of sulfur may have a concentration gradient where the concentration of sulfur varies radially (e.g., decreases or increases in the direction towards the core).
[0172] In an embodiment, the semiconductor nanoparticle may emit red or green light, the core may include InP, InZnP, or a combination thereof, and the shell may include group II metals and non-metals, the group II metal including zinc, and the non-metal including sulfur, selenium, or a combination thereof.
[0173] In an embodiment, the semiconductor nanoparticle may have a core-shell structure, and at the interface between the core and the shell, an alloyed intermediate layer may or may not be present. The alloyed intermediate layer may include a homogeneous alloy or may have a concentration gradient. The gradient alloy may have a concentration gradient such that the concentration of the elements of the shell varies radially (e.g., decreases or increases in the direction towards the core).
[0174] In an embodiment, the shell may have a composition that varies in the radial direction. In an embodiment, the shell may be a multi-layer shell including two or more layers. In the multi-layer shell, adjacent two layers may have different compositions from each other. In the multi-layer shell, a layer, such as at least one layer, may independently include semiconductor nanocrystals having a single composition. In the multi-layer shell, a layer, such as at least one layer, may independently have alloyed semiconductor nanocrystals. In the multi-layer shell, a layer, such as at least one layer, may have a concentration gradient that varies radially in terms of the composition of the semiconductor nanocrystals.
[0175] In an embodiment, in a semiconductor nanoparticle having a core-shell structure, the shell material may have a bandgap energy greater than that of the core. The material of the shell may have a bandgap energy less than that of the core. In the case of a multi-layer shell, the bandgap energy of the outermost layer material of the shell may be greater than the bandgap energies of the core and the inner layer materials (the layers closer to the core) of the shell. In the case of a multi-layer shell, the semiconductor nanocrystals of each layer are selected to have an appropriate bandgap so as to effectively exhibit the quantum confinement effect.
[0176] The absorption or emission wavelength of the semiconductor nanoparticle can be controlled by adjusting the composition of the semiconductor nanoparticle, the particle size, or a combination thereof. The semiconductor nanoparticles included in the light-emitting layer 3 or 30 may emit light of a desired color. The semiconductor nanoparticles may include blue light-emitting semiconductor nanoparticles, green light-emitting semiconductor nanoparticles, or red light-emitting semiconductor nanoparticles. In an embodiment, the light-emitting layer may be configured to emit blue light, green light, or red light, and the wavelengths of the blue light, green light, and red light are as described herein.
[0177] In an embodiment, the peak emission wavelength of the semiconductor nanoparticles or the light-emitting layer (or the light emitted from the electroluminescent device) can be within the wavelength range from ultraviolet to infrared. In an embodiment, the peak emission wavelength of the semiconductor nanoparticles or the light-emitting layer (or the light emitted from the electroluminescent device) can be greater than or equal to about 300 nm, greater than or equal to about 500 nm, greater than or equal to about 510 nm, greater than or equal to about 520 nm, greater than or equal to about 530 nm, greater than or equal to about 540 nm, greater than or equal to about 550 nm, greater than or equal to about 560 nm, greater than or equal to about 570 nm, greater than or equal to about 580 nm, greater than or equal to about 590 nm, greater than or equal to about 600 nm, or greater than or equal to about 610 nm. The peak emission wavelength can be less than or equal to about 800 nm, less than or equal to about 650 nm, less than or equal to about 640 nm, less than or equal to about 630 nm, less than or equal to about 620 nm, less than or equal to about 610 nm, less than or equal to about 600 nm, less than or equal to about 590 nm, less than or equal to about 580 nm, less than or equal to about 570 nm, less than or equal to about 560 nm, less than or equal to about 550 nm, or less than or equal to about 540 nm. The peak emission wavelength can be from about 500 nm to about 650 nm.
[0178] The semiconductor nanoparticles, the light-emitting layer or the electroluminescent device can emit green light (e.g., when a voltage is applied or irradiated with light), and its peak emission wavelength can be within the range of greater than or equal to about 500 nm (e.g., greater than or equal to about 510 nm, or greater than or equal to about 515 nm) and less than or equal to about 560 nm, such as less than or equal to about 540 nm, or less than or equal to about 530 nm. The semiconductor nanoparticles, the light-emitting layer or the electroluminescent device can emit red light (e.g., when a voltage is applied or irradiated with light), and its peak emission wavelength can be within the range of greater than or equal to about 600 nm, such as greater than or equal to about 610 nm and less than or equal to about 650 nm, or less than or equal to about 640 nm. The semiconductor nanoparticles, the light-emitting layer or the electroluminescent device can emit blue light (e.g., when a voltage is applied or irradiated with light), and its peak emission wavelength can be greater than or equal to about 430 nm (e.g., greater than or equal to about 450 nm, greater than or equal to about 455 nm, greater than or equal to about 460 nm, or greater than or equal to about 465 nm) and less than or equal to about 480 nm (e.g., less than or equal to about 475 nm, less than or equal to about 470 nm, or less than or equal to about 465 nm).
[0179] In an embodiment, the semiconductor nanoparticles, the light-emitting layer, or the electroluminescent device may exhibit a luminescence spectrum (e.g., a photoluminescence spectrum or an electroluminescence spectrum) having a relatively narrow full width at half maximum. In an embodiment, in the photoluminescence or electroluminescence spectrum, the semiconductor nanoparticles, the light-emitting layer, or the electroluminescent device may exhibit a full width at half maximum that is less than or equal to about 45 nm, less than or equal to about 44 nm, less than or equal to about 43 nm, less than or equal to about 42 nm, less than or equal to about 41 nm, less than or equal to about 40 nm, less than or equal to about 39 nm, less than or equal to about 38 nm, less than or equal to about 37 nm, less than or equal to about 36 nm, or less than or equal to about 35 nm. The full width at half maximum may be greater than or equal to about 10 nm, greater than or equal to about 15 nm, greater than or equal to about 20 nm, or greater than or equal to about 25 nm.
[0180] The semiconductor nanoparticles may have a quantum yield as follows: greater than or equal to about 10%, e.g., greater than or equal to about 20%, greater than or equal to about 30%, greater than or equal to about 40%, greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 80%, greater than or equal to about 90%, or even about 100% (e.g., configured to achieve this). In an embodiment, the semiconductor nanoparticles may have a quantum yield (or absolute quantum yield) that is greater than or equal to about 91%, greater than or equal to about 92%, greater than or equal to about 93%, greater than or equal to about 94%, greater than or equal to about 95%, greater than or equal to about 96%, or greater than or equal to about 97%.
[0181] The semiconductor nanoparticles may have a size (or average size, which may be simply referred to as "size" hereinafter) greater than or equal to about 1 nm and less than or equal to about 100 nm. The size may be a diameter or an equivalent diameter converted from an electron microscope image by assuming a spherical shape when it is not spherical. The size can be calculated from the results of inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis. In an embodiment, the semiconductor nanoparticles may have a size of about 1 nm to about 50 nm, such as about 2 nm (or about 3 nm) to about 35 nm. In an embodiment, the size (or average size) of the semiconductor nanoparticles may be greater than or equal to about 3 nm, greater than or equal to about 4 nm, greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, greater than or equal to about 10 nm, greater than or equal to about 11 nm, greater than or equal to about 12 nm, greater than or equal to about 13 nm, or greater than or equal to about 14 nm. In an embodiment, the size of the semiconductor nanoparticles may be less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, less than or equal to about 25 nm, less than or equal to about 20 nm, less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, less than or equal to about 16 nm, less than or equal to about 15 nm, less than or equal to about 14 nm, less than or equal to about 13 nm, or less than or equal to about 12 nm.
[0182] The shape of the semiconductor nanoparticles or semiconductor nanostructures is not particularly limited. For example, the shape of the semiconductor nanoparticles may include, but is not limited to, spheres, polyhedra, pyramids, multi-legged shapes, hexahedrons, cubes, cuboids, nanotubes, nanorods, nanowires, or nanosheets.
[0183] As luminescent materials, there is a growing interest in electroluminescent devices including inorganic-based semiconductor nanoparticles. Electroluminescent devices based on semiconductor nanoparticles (e.g., QD light-emitting diodes, QD-LEDs) utilize the electroluminescence of semiconductor nanoparticles through the injection and recombination of electrons and holes in semiconductor nanoparticles such as quantum dots, and have high potential for various electronic devices (e.g., display devices). Electroluminescent devices based on semiconductor nanoparticles may not require a separate backlight and can be provided in a thin structure. Therefore, active research is being conducted in multiple fields to modify semiconductor nanoparticles to improve the performance of electroluminescent devices. For example, research is being carried out on electroluminescent devices including cadmium-free quantum dots that do not contain harmful heavy metals such as cadmium. One area of concern is core-shell semiconductor nanoparticles, which have a core including a first semiconductor nanocrystal and a semiconductor nanocrystal shell disposed on the core. Additionally, research is being conducted to provide such QD LED devices through cost-effective solution processes such as inkjet printing methods.
[0184] The present inventors have found that in the prior art, the Zn precursor used during the growth of the shell (e.g., the outermost shell including zinc sulfide) can not only affect the shell coating quality of the resulting semiconductor nanoparticles, but also affect the composition of the organic ligands of the semiconductor nanoparticles. Without wishing to be bound by any theory, it is considered that in the Zn precursors according to the prior art, it is difficult to provide a desired level of coating speed, and there may be a relatively high lattice strain at the growth interface. Additionally, the Zn precursor used in forming the outermost layer in the prior art may include a relatively long organic chain, which can affect the electroluminescent properties of the QD-LED device and hinder the improvement of the device lifetime.
[0185] Regarding the organic ligand composition, short-chain organic ligands or inorganic ligands (e.g., halides) can be used in place of the organic ligands having a relatively long organic chain. However, the prior art methods inevitably involve additional processes (e.g., a separate ligand exchange process) to control the ligand composition of the semiconductor nanoparticles, which not only increases the manufacturing cost but also has technical drawbacks (i.e., adversely affects the luminescent properties of the resulting semiconductor nanoparticles). Furthermore, the present inventors have also found that organic ligands having a relatively long organic chain disposed on the surface of the semiconductor nanoparticles can be advantageous for improving the dispersion properties of the particles (e.g., when halides coexist), but when included in the device, they may adversely affect the properties of the device such as lifetime.
[0186] In an embodiment, in forming a semiconductor nanocrystal shell (or outermost shell layer) comprising zinc sulfide, a zinc precursor (e.g., a first zinc precursor) having a carboxylate moiety derived from a carboxylic acid having a relatively low acid dissociation constant (pKa) (e.g., less than or equal to about 8, or less than or equal to about 7.5) is used in combination with a zinc precursor (a second zinc precursor) having a carboxylate moiety derived from a carboxylic acid having a relatively high acid dissociation constant (e.g., greater than or equal to about 8.8, or greater than or equal to about 9 and less than or equal to about 12) in the manner described herein, and the use of a metal halide is also employed. The inventors have surprisingly found that, based on the method described herein, combining the zinc precursors during the synthesis of semiconductor nanoparticles provides high-quality shell coating at a desired coating rate and also provides semiconductor nanoparticles having an optimized ligand composition. Without wishing to be bound by any theory, it is believed that, in an embodiment, the combination of the first zinc precursor and the second zinc precursor allows the reaction rate of shell formation to be controlled within a desired range and reduces the lattice strain at the growth interface of the semiconductor nanocrystal shell. The combination of the first zinc precursor and the second zinc precursor can help to inhibit particle aggregation due to the addition of the metal halide, and the semiconductor nanoparticles thus prepared comprise the ligand system described herein, which enables improved dispersion properties required for solution processes such as inkjet processes and minimizes the adverse effects on electroluminescent properties and device lifetime that may otherwise occur without the ligand system.
[0187] Thus, the semiconductor nanoparticles of the embodiment further comprise a plurality of organic ligands or a ligand system comprising them. The plurality of organic ligands or the ligand system may be bound to or disposed on the surface of the semiconductor nanoparticles (or the semiconductor nanocrystal shell). The semiconductor nanoparticles or the ligand system may further comprise a halogen (e.g., a halide (halide radical)).
[0188] The ligand system or the plurality of organic ligands may comprise hydrocarbon groups. The total number of carbon atoms in the ligand system or the plurality of organic ligand molecules (or molecular formulas) may be greater than or equal to about 20, greater than or equal to about 21, greater than or equal to about 22, greater than or equal to about 23, greater than or equal to about 24, greater than or equal to about 25, greater than or equal to about 26, greater than or equal to about 27, greater than or equal to about 28, or greater than or equal to about 29. The total number of carbon atoms may be less than or equal to about 40, less than or equal to about 38, less than or equal to about 36, less than or equal to about 35, less than or equal to about 34, less than or equal to about 33, less than or equal to about 32, less than or equal to about 31, less than or equal to about 30, less than or equal to about 29, less than or equal to about 28, or less than or equal to about 27.
[0189] The ligand system or multiple organic ligands may include: a first organic ligand having a carboxylate moiety; and a second organic ligand different from the first organic ligand and also having a carboxylate moiety. The first organic ligand may be derived from a first zinc precursor (as described herein). The second organic ligand may be derived from a second zinc precursor (as described herein). The molecular weight (or the number of carbon atoms) of the second organic ligand may be greater than the molecular weight (or the number of carbon atoms) of the first organic ligand.
[0190] The first organic ligand may have a molecular weight greater than or equal to about 90 g / mol, greater than or equal to about 100 g / mol, greater than or equal to about 105 g / mol, greater than or equal to about 110 g / mol, greater than or equal to about 115 g / mol, greater than or equal to about 120 g / mol, greater than or equal to about 125 g / mol, greater than or equal to about 130 g / mol, greater than or equal to about 140 g / mol, greater than or equal to about 150 g / mol, greater than or equal to about 160 g / mol, greater than or equal to about 170 g / mol, greater than or equal to about 180 g / mol, greater than or equal to about 190 g / mol, or greater than or equal to about 200 g / mol. The first organic ligand may have a molecular weight less than or equal to about 257 g / mol, less than or equal to about 230 g / mol, less than or equal to about 225 g / mol, less than or equal to about 220 g / mol, less than or equal to about 215 g / mol, less than or equal to about 210 g / mol, less than or equal to about 200 g / mol, less than or equal to about 190 g / mol, less than or equal to about 180 g / mol, less than or equal to about 170 g / mol, less than or equal to about 160 g / mol, less than or equal to about 155 g / mol, less than or equal to about 150 g / mol, less than or equal to about 145 g / mol, less than or equal to about 140 g / mol, or less than or equal to about 130 g / mol.
[0191] The first organic ligand may include a hydrocarbon group, such as an aliphatic, aromatic or cycloaliphatic hydrocarbon group. The hydrocarbon group of the first organic ligand may include a substituted or unsubstituted C6-C18 aromatic hydrocarbon group, or a substituted or unsubstituted C2-C16, C2-C14, C3-C12, C4-C10, C5-C9, C4-C8 or C6-C7 straight-chain or branched aliphatic hydrocarbon group (e.g., an alkyl, alkenyl or alkynyl group). The first organic ligand may include a branched alkyl group. The first organic ligand may include a propionate (propionic acid group) moiety, an isopropionate (isopropionic acid group) moiety, a butyrate (butyric acid group) moiety, a butyrate (butyric acid group) moiety having one or more C1-C3 alkyl groups (e.g., a methylbutyrate moiety or an ethylbutyrate moiety), a valerate (valeric acid group) moiety, a valerate (valeric acid group) moiety substituted with one or more C1-C4 alkyl groups (e.g., a methylvalerate moiety or a propylvalerate moiety), a caproate (caproic acid group) moiety, a caproate (caproic acid group) moiety substituted with one or more C1-C5 alkyl groups (e.g., an ethylcaproate (ethylcaproic acid group) moiety), a caprylate (caprylic acid group) moiety, a caprylate (caprylic acid group) moiety substituted with a C1-C6 alkyl group (e.g., a butylcaprylate (butylcaprylic acid group) moiety), or a combination thereof.
[0192] The first organic ligand may include a carboxylate moiety (e.g., a carboxylate anion) represented by Chemical Formula 1, and the total number of carbon atoms in the first organic ligand is 3 to 15, or 4 to 13, or 5 to 11, or 6 to 10:
[0193] Chemical Formula 1
[0194]
[0195] where R is the same or different and each independently is hydrogen or a C1-C6, or C2-C4, or C3-C5 alkyl group (e.g., methyl, ethyl, propyl, butyl, pentyl, or hexyl), and n is an integer from 1 to 14, or 2 to 12, or 3 to 10, or 4 to 8.
[0196] The second organic ligand may have a larger molecular weight or a greater number of carbon atoms than the first organic ligand. The difference in molecular weight between the second organic ligand and the first organic ligand may be greater than or equal to about 50 g / mol, greater than or equal to about 75 g / mol, greater than or equal to about 80 g / mol, greater than or equal to about 90 g / mol, greater than or equal to about 100 g / mol, greater than or equal to about 120 g / mol, greater than or equal to about 130 g / mol, or greater than or equal to about 150 g / mol. The difference in molecular weight between the second organic ligand and the first organic ligand may be less than or equal to about 240 g / mol, less than or equal to about 220 g / mol, less than or equal to about 200 g / mol, less than or equal to about 180 g / mol, less than or equal to about 160 g / mol, less than or equal to about 150 g / mol, less than or equal to about 140 g / mol, less than or equal to about 130 g / mol, less than or equal to about 120 g / mol, less than or equal to about 100 g / mol, or less than or equal to about 90 g / mol.
[0197] The second organic ligand may have a molecular weight greater than about 200 g / mol, greater than or equal to about 210 g / mol, greater than or equal to about 215 g / mol, greater than or equal to about 220 g / mol, greater than or equal to about 225 g / mol, greater than or equal to about 230 g / mol, greater than or equal to about 235 g / mol, greater than or equal to about 240 g / mol, greater than or equal to about 245 g / mol, greater than or equal to about 250 g / mol, greater than or equal to about 255 g / mol, greater than or equal to about 260 g / mol, greater than or equal to about 265 g / mol, greater than or equal to about 270 g / mol, or greater than or equal to about 280 g / mol. The second organic ligand may have a molecular weight less than or equal to about 500 g / mol, less than or equal to about 450 g / mol, less than or equal to about 440 g / mol, less than or equal to about 430 g / mol, less than or equal to about 420 g / mol, less than or equal to about 410 g / mol, less than or equal to about 400 g / mol, less than or equal to about 390 g / mol, less than or equal to about 380 g / mol, less than or equal to about 370 g / mol, less than or equal to about 360 g / mol, less than or equal to about 350 g / mol, less than or equal to about 340 g / mol, or less than or equal to about 250 g / mol.
[0198] The second organic ligand may include an aliphatic hydrocarbon group having a straight or branched chain of C12-C25, C13-C23, C14-C22, C16-C21, C17-C20 or C18-C19 (e.g., an alkyl, alkenyl or alkynyl group). The second organic ligand may include a tetradecyl group, a tetradecenyl group, a pentadecyl group, a pentadecenyl group, a hexadecyl group, a hexadecenyl group, a heptadecyl group, a heptadecenyl group, an octadecyl group, an octadecenyl group, an octadecadienyl group, an octadecatrienyl group, or a combination thereof.
[0199] The second organic ligand may include, for example, a carbon-carbon double bond within the aliphatic hydrocarbon group chain. The second organic ligand may include a linolenate (linolenyl) moiety, a linoleate (linoleyl) moiety, an oleate (oleyl) moiety, an elaidate (elaidyl) moiety, a stearate (stearyl) moiety, a palmitate (palmitoyl) moiety, a myristate (myristoyl) moiety, or a combination thereof.
[0200] In an embodiment, the first organic ligand may include a branched alkyl group and the second organic ligand may include a straight-chain alkenyl group.
[0201] In an embodiment, the semiconductor nanoparticles can include both a first organic ligand and a second organic ligand, and in a gas chromatography (GC) analysis (e.g., in a chromatogram obtained by gas chromatography analysis), a first peak attributable to the first organic ligand and a second peak attributable to the second organic ligand can be shown. In the semiconductor nanoparticles of the embodiment, the area percentage of the first peak relative to the second peak can be greater than or equal to about 1%, or greater than or equal to about 3% and less than or equal to about 200%, or less than or equal to about 99%. In an embodiment, the area percentage of the first peak relative to the second peak can be greater than or equal to about 5%, greater than or equal to about 7%, greater than or equal to about 10%, greater than or equal to about 15%, greater than or equal to about 17%, greater than or equal to about 19%, greater than or equal to about 20%, greater than or equal to about 21%, greater than or equal to about 23%, greater than or equal to about 25%, greater than or equal to about 27%, greater than or equal to about 29%, greater than or equal to about 30%, greater than or equal to about 31%, greater than or equal to about 33%, greater than or equal to about 35%, greater than or equal to about 37%, greater than or equal to about 39%, greater than or equal to about 40%, greater than or equal to about 41%, greater than or equal to about 43%, greater than or equal to about 45%, greater than or equal to about 47%, greater than or equal to about 49%, greater than or equal to about 50%, greater than or equal to about 51%, greater than or equal to about 53%, greater than or equal to about 55%, greater than or equal to about 57%, greater than or equal to about 59%, greater than or equal to about 60%, greater than or equal to about 61%, greater than or equal to about 63%, greater than or equal to about 65%, greater than or equal to about 67%, greater than or equal to about 69%, greater than or equal to about 70%, greater than or equal to about 71%, greater than or equal to about 73%, greater than or equal to about 75%, greater than or equal to about 77%, greater than or equal to about 79%, greater than or equal to about 81%, greater than or equal to about 83%, greater than or equal to about 85%, greater than or equal to about 87%, greater than or equal to about 89%, greater than or equal to about 90%, greater than or equal to about 91%, greater than or equal to about 93%, greater than or equal to about 95%, greater than or equal to about 97%, greater than or equal to about 99%, greater than or equal to about 100%, greater than or equal to about 101%, greater than or equal to about 103%, greater than or equal to about 105%, greater than or equal to about 107%, greater than or equal to about 109%, or greater than or equal to about 110%. The area percentage of the first peak relative to the second peak can be less than or equal to about 400%, less than or equal to about 350%, less than or equal to about 300%, less than or equal to about 250%, less than or equal to about 200%, less than or equal to about 190%, less than or equal to about 180%, less than or equal to about 170%, less than or equal to about 160%, less than or equal to about 150%, less than or equal to about 140%, less than or equal to about 130%, less than or equal to about 120%, less than or equal to about 110%, less than or equal to about 98%, or less than or equal to about 97%.
[0202] The retention time (i.e., the collection time) of the second peak can be longer than the retention time of the first peak. The ratio of the retention time of the first peak (the elution time of the first organic ligand peak) to the retention time of the second peak (the elution time of the second organic ligand peak) can be greater than or equal to about 0.1:1, greater than or equal to about 0.2:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.6:1, or greater than or equal to about 0.7:1. The ratio of the retention times can be less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.8:1, or less than or equal to about 0.7:1. The difference in retention time between the second peak and the first peak can be greater than or equal to about 1 minute, greater than or equal to about 2 minutes, greater than or equal to about 3 minutes, greater than or equal to about 4 minutes, or greater than or equal to about 5 minutes, greater than or equal to about 6 minutes, greater than or equal to about 7 minutes, greater than or equal to about 8 minutes, greater than or equal to about 9 minutes, greater than or equal to about 10 minutes. The difference in retention time between the second peak and the first peak can be less than or equal to about 15 minutes, less than or equal to about 13 minutes, less than or equal to about 12 minutes, less than or equal to about 11 minutes, less than or equal to about 10 minutes, less than or equal to about 9 minutes, less than or equal to about 7 minutes, less than or equal to about 5 minutes, or less than or equal to about 2 minutes.
[0203] Gas chromatography (GC) is an analytical technique that can be used to separate, identify, and quantify the chemical components in a complex mixture. In GC, a gas carries the sample through the GC instrument. In an embodiment, the carrier gas or mobile phase is not particularly limited and can be high-purity helium, hydrogen, or nitrogen. In an embodiment, the gas chromatography analysis device can include a syringe (e.g., a split / splitless (SSL) syringe), a column (e.g., a wall-coated open-tubular (WCOT) capillary column including a thin layer of a dimethyl polysiloxane stationary phase), and a detector (e.g., a flame ionization detector FID or mass spectrometry MS), but is not limited thereto. In an embodiment, the GC column can be a capillary column and can be a fused silica capillary including a polymer outer coating. In the chromatogram obtained by GC, the x-axis represents the retention time (typically in minutes), and the y-axis represents the detector response. In an embodiment, the GC device can be py-GC / MS. In GC, the temperature of the pyrolyzer can be from 400 °C to 600 °C or from 450 °C to 550 °C. The GC device can include a capillary column. The capillary column can include a stationary phase of polysiloxane (e.g., dimethyl polysiloxane, 5% to 65% diphenyldimethyl polysiloxane, polyethylene glycol, etc.), and the polarity can be appropriately selected.
[0204] The flow rate of the mobile phase (gas) can be appropriately selected and can be in the range of 0.5 milliliters per minute (mL / min) to 10 mL / min, or 1 mL / min to 5 mL / min, or 1.5 mL / min to 3 mL / min. The inlet temperature of the GC device can be appropriately selected and can be in the range of 100 °C to 400 °C, 150 °C to 300 °C, or 200 °C to 250 °C. The GC oven temperature (oven temperature) can be appropriately controlled. The analyzer can be a quadrupole (range: 10 - 550 mass-to-charge ratio (m / z)).
[0205] As confirmed by thermogravimetric analysis, the semiconductor nanoparticles of the embodiments can exhibit a relatively reduced organic content, but can still show a desired level of dispersion in organic solvents (e.g., aliphatic hydrocarbon solvents such as octane). In the thermogravimetric analysis, the semiconductor nanoparticles of the embodiments can exhibit a weight loss in the range of 200 °C to 550 °C as follows: less than or equal to about 13 weight percent (wt%), less than or equal to about 12 wt%, less than or equal to about 11.5 wt%, less than or equal to about 10.5 wt%, less than or equal to about 10 wt%, less than or equal to about 9.5 wt%, or less than or equal to about 8 wt%, based on the total weight of the semiconductor nanoparticles. In the thermogravimetric analysis, the semiconductor nanoparticles can exhibit a weight loss in the range of 200 °C to 550 °C as follows: greater than or equal to about 1 wt%, greater than or equal to about 3 wt%, greater than or equal to about 5 wt%, or greater than or equal to about 7 wt%, based on the total weight of the semiconductor nanoparticles.
[0206] In the thermogravimetric analysis, the semiconductor nanoparticles can have a residual content at a temperature of about 550 °C or higher as follows: greater than or equal to about 80 wt%, greater than or equal to about 83 wt%, greater than or equal to about 87 wt%, or greater than or equal to about 88 wt%, or greater than or equal to about 90 wt%, or greater than or equal to about 91 wt% and less than or equal to about 99 wt%, less than or equal to about 97 wt%, less than or equal to about 92 wt%, or less than or equal to about 90 wt%, based on the total weight of the semiconductor nanoparticles.
[0207] Semiconductor nanoparticles can exhibit improved dispersibility in organic solvents (e.g., aliphatic hydrocarbon solvents such as octane). In an embodiment, when dispersed in octane and measured by dynamic light scattering analysis, the semiconductor nanoparticles can exhibit a DLS particle diameter less than about 300 nm. The DLS particle diameter can be less than or equal to about 200 nm, less than or equal to about 100 nm, less than or equal to about 80 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, or less than or equal to about 20 nm. The DLS particle diameter can be greater than or equal to about 5 nm, greater than or equal to about 7 nm, greater than or equal to about 10 nm, greater than or equal to about 15 nm, or greater than or equal to about 20 nm.
[0208] The semiconductor nanoparticles can further include a halogen, e.g., in the form of a halide (halide ion). The halogen can be fluorine, chlorine, bromine, iodine, or a combination thereof. In an embodiment, the halogen can be chlorine, e.g., chloride (chloride ion).
[0209] In the semiconductor nanoparticles, the molar ratio of halogen to zinc can be greater than or equal to about 0.005:1, greater than or equal to about 0.01:1, greater than or equal to about 0.02:1, greater than or equal to about 0.03:1, greater than or equal to about 0.04:1, greater than or equal to about 0.05:1, greater than or equal to about 0.08:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, or greater than or equal to about 0.2:1. In the semiconductor nanoparticles, the molar ratio of halogen to zinc can be less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.4:1, less than or equal to about 0.2:1, less than or equal to about 0.12:1, less than or equal to about 0.09:1, less than or equal to about 0.07:1, less than or equal to about 0.06:1, or less than or equal to about 0.05:1.
[0210] In the semiconductor nanoparticles, the molar ratio of halogen to selenium can be greater than or equal to about 0.005:1, greater than or equal to about 0.01:1, greater than or equal to about 0.02:1, greater than or equal to about 0.03:1, greater than or equal to about 0.04:1, greater than or equal to about 0.05:1, greater than or equal to about 0.08:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, or greater than or equal to about 0.2:1. In the semiconductor nanoparticles, the molar ratio of halogen to selenium can be less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.7:1, less than or equal to about 0.6:1, less than or equal to about 0.4:1, less than or equal to about 0.2:1, less than or equal to about 0.12:1, less than or equal to about 0.09:1, less than or equal to about 0.07:1, less than or equal to about 0.06:1, or less than or equal to about 0.05:1.
[0211] In the semiconductor nanoparticles, the molar ratio of carbon to zinc can be greater than or equal to about 0.005:1, greater than or equal to about 0.01:1, greater than or equal to about 0.05:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.25:1, greater than or equal to about 0.3:1, greater than or equal to about 0.35:1, greater than or equal to about 0.4:1, or greater than or equal to about 0.45:1. In the semiconductor nanoparticles, the molar ratio of carbon to zinc can be less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.7:1, or less than or equal to about 0.5:1.
[0212] In the semiconductor nanoparticles, the molar ratio of carbon to selenium can be greater than or equal to about 0.005:1, greater than or equal to about 0.01:1, greater than or equal to about 0.05:1, greater than or equal to about 0.1:1, greater than or equal to about 0.15:1, greater than or equal to about 0.2:1, greater than or equal to about 0.3:1, greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.7:1, greater than or equal to about 0.8:1, greater than or equal to about 0.9:1, or greater than or equal to about 0.95:1. In the semiconductor nanoparticles, the molar ratio of carbon to selenium can be less than or equal to about 2:1, less than or equal to about 1.5:1, less than or equal to about 1:1, less than or equal to about 0.9:1, less than or equal to about 0.7:1, or less than or equal to about 0.5:1.
[0213] In semiconductor nanoparticles, the molar ratio of sulfur to selenium can be greater than or equal to about 0.4:1, greater than or equal to about 0.5:1, greater than or equal to about 0.6:1, greater than or equal to about 0.7:1, greater than or equal to about 0.8:1, or greater than or equal to about 0.9:1. In semiconductor nanoparticles, the molar ratio of sulfur to selenium can be less than or equal to about 1:1, less than or equal to about 0.95:1, less than or equal to about 0.85:1, less than or equal to about 0.75:1, less than or equal to about 0.65:1, less than or equal to about 0.55:1, or less than or equal to about 0.45:1.
[0214] The molar amount of an element or the molar ratio between elements as described herein (e.g., included in semiconductor nanoparticles or a light-emitting layer) can be determined by, for example, using suitable analytical tools (e.g., inductively coupled plasma atomic emission spectrometry (ICP-AES), X-ray photoelectron spectroscopy (XPS), ion chromatography, transmission electron microscopy energy-dispersive X-ray spectroscopy (TEM-EDX), scanning electron microscopy energy-dispersive X-ray spectroscopy (SEM-EDX), X-ray fluorescence (XRF), or a combination thereof).
[0215] In an embodiment, the semiconductor nanoparticles can exhibit an average lifetime (or average decay time) of greater than or equal to about 20 ns, greater than or equal to about 30 ns, greater than or equal to about 40 ns, greater than or equal to about 45 ns, or greater than or equal to about 50 ns in time-resolved photoluminescence spectroscopy analysis. In time-resolved photoluminescence spectroscopy analysis, the average lifetime (or average decay time) of the semiconductor nanoparticles can be less than or equal to about 500 ns, less than or equal to about 300 ns, less than or equal to about 100 ns, less than or equal to about 90 ns, less than or equal to about 80 ns, or less than or equal to about 75 ns.
[0216] The semiconductor nanoparticles can be synthesized by the methods described herein.
[0217] The method of an embodiment can include synthesizing semiconductor nanocrystals of a few nanometers in size by a wet chemical process. In the wet chemical process, precursor materials react in an organic solvent to form crystal particles, and the growth of the crystals can be controlled by coordinating an organic solvent or a ligand compound to the surface of the semiconductor nanocrystals. In an embodiment, the method for manufacturing semiconductor nanoparticles can include preparing particles comprising a first semiconductor nanocrystal and optionally a second semiconductor nanocrystal.
[0218] Details of the first semiconductor nanocrystal and the second semiconductor nanocrystal are as described herein. In an embodiment of the method, if present, the second semiconductor nanocrystal may include zinc and selenium (e.g., ZnSe, ZnSeS, or a combination thereof). The second semiconductor nanocrystal may be disposed on the first semiconductor nanocrystal. The second semiconductor nanocrystal may be an intermediate shell layer of semiconductor nanoparticles.
[0219] In an embodiment of the method, the preparation of the particles including the first semiconductor nanocrystal and optionally the second semiconductor nanocrystal is not particularly limited and may be appropriately selected.
[0220] In an embodiment, the first semiconductor nanocrystal or the core including it may include zinc and selenium, and optionally tellurium. The first semiconductor nanocrystal or the core including the first semiconductor nanocrystal may include indium phosphide. In an embodiment, the first semiconductor nanocrystal or the core including the first semiconductor nanocrystal may include ZnSe, ZnSeTe, InP, InZnP, or a combination thereof. In an embodiment, the first semiconductor nanocrystal or the core including the first semiconductor nanocrystal may be manufactured by an appropriate method considering the composition and desired properties of the final nanoparticles, or may be commercially available.
[0221] In an embodiment, the first semiconductor nanocrystal or the core may include a zinc chalcogenide including zinc, selenium, and tellurium, and the first semiconductor nanocrystal or the core may be obtained by: preparing a zinc precursor solution including a zinc precursor and an organic ligand; preparing a selenium precursor and a tellurium precursor; heating the zinc precursor solution to a nucleation reaction temperature, and adding the selenium precursor and the tellurium precursor, and optionally the organic ligand, and performing a nucleation reaction.
[0222] In an embodiment, the first semiconductor nanocrystal or the core including the first semiconductor nanocrystal may be formed by a thermal injection method, in which a solution including a metal precursor such as an indium precursor and optionally a ligand is heated to a high temperature (e.g., to a temperature of greater than or equal to about 200 °C) and a phosphorus precursor is injected. In an embodiment, the core may be prepared by a heating (temperature raising) method, in which a phosphorus precursor is injected at a predetermined temperature and the temperature of the reaction system is raised.
[0223] In the nucleation reaction, the ratio between precursors (e.g., the molar ratio of a selenium precursor to a tellurium precursor) or the reaction time can be appropriately selected in consideration of the emission wavelength of the final semiconductor nanoparticles, the reactivity of the precursors, and the reaction temperature. The nucleation reaction temperature can be appropriately selected. The nucleation reaction temperature can be greater than or equal to about 240 °C, greater than or equal to about 250 °C, greater than or equal to about 260 °C, greater than or equal to about 270 °C, greater than or equal to about 280 °C, for example greater than or equal to about 290 °C. The reaction temperature for nucleation can be in the range of about 280 °C to about 340 °C, for example about 290 °C to about 330 °C, or about 300 °C to about 320 °C. The reaction time for nucleation can be adjusted in consideration of the desired nucleus size and the reactivity of the precursors, and there is no particular limitation. For example, the reaction time can be greater than or equal to about 5 minutes, greater than or equal to about 30 minutes, or greater than or equal to about 50 minutes, but is not limited thereto. For example, the reaction time can be less than or equal to about 2 hours, but is not limited thereto. The formed nuclei can be separated from the reaction system (e.g., by nonsolvent precipitation) or not separated. The separated nuclei can be washed (if necessary) and added to the subsequent reaction.
[0224] The semiconductor nanoparticles of the embodiments can further include a second semiconductor nanocrystal or an intermediate shell layer including a second semiconductor nanocrystal, and the method for forming the second semiconductor nanocrystal or the intermediate shell layer including a second semiconductor nanocrystal is not particularly limited and can be appropriately selected.
[0225] In an embodiment of the method, forming a second semiconductor nanocrystal (or an intermediate shell layer including a second semiconductor nanocrystal) on the first semiconductor nanocrystal can include mixing (reacting) a zinc precursor with a chalcogen precursor (e.g., a selenium precursor and optionally a sulfur precursor) at a reaction temperature in the presence of an organic solvent and the first semiconductor nanocrystal.
[0226] The organic ligand, organic solvent, and precursor are not particularly limited and can be appropriately selected.
[0227] The organic solvent can include: C6-C22 primary amines such as hexadecylamine; C6-C22 secondary amines such as dioctylamine; C6-C40 tertiary amines such as trioctylamine; nitrogen-containing heterocyclic compounds such as pyridine; C6-C40 olefins such as octadecene; C6-C40 aliphatic hydrocarbons such as hexadecane, octadecane, or squalane; aromatic hydrocarbons substituted with C6-C30 alkyl groups such as phenyldodecane, phenyltetradecane, or phenylhexadecane; primary, secondary, or tertiary phosphines (e.g., trioctylphosphine) substituted with at least one (e.g., 1, 2, or 3) C6-C22 alkyl groups; phosphine oxides (e.g., trioctylphosphine oxide) substituted with (e.g., 1, 2, or 3) C6-C22 alkyl groups; C12-C22 aromatic ethers such as phenyl ether or benzyl ether; or a combination thereof.
[0228] The organic ligand can coordinate to the surface of the prepared semiconductor nanoparticles and allow the semiconductor nanoparticles to be well dispersed in the solution. The organic ligand can include RCOOH, RNH2, R2NH, R3N, RSH, RH2PO, R2HPO, R3PO, RH2P, R2HP, R3P, ROH, RCOOR', RPO(OH)2, R2POOH (where R and R' independently include a substituted or unsubstituted aliphatic hydrocarbon group having 1 or more, 6 or more, or 10 or more and 40 or less, 35 or less, or 25 or less carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having 6-40 carbon atoms, or a combination thereof), or a combination thereof. The ligand can be used alone or as a combination of two or more compounds.
[0229] There is no particular limitation on the type of indium precursor, and it can be appropriately selected. The indium precursor can include indium powder, alkylated indium compounds, indium alkoxides, indium carboxylates, indium nitrate, indium perchlorate, indium sulfate, indium acetylacetonate, indium halides, indium cyanide, indium hydroxide, indium oxide, indium peroxide, indium carbonate, indium acetate or a combination thereof. The indium precursor can include indium carboxylates (such as indium oleate and indium myristate), indium acetate, indium hydroxide, indium chloride, indium bromide, indium iodide or a combination thereof.
[0230] There is no particular limitation on the type of phosphorus precursor, and it can be appropriately selected. The phosphorus precursor can include tris(trimethylsilyl)phosphine, tris(dimethylamino)phosphine, triethylphosphine, tributylphosphine, trioctylphosphine, triphenylphosphine, tricyclohexylphosphine, dimethylaminophosphine, diethylaminophosphine or a combination thereof.
[0231] Examples of organic ligands can include: methanethiol, ethanethiol, propanethiol, butanethiol, pentanethiol, hexanethiol, heptanethiol, octanethiol, nonanethiol, decanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, benzyl mercaptan; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine; formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, benzoic acid; substituted or unsubstituted methylphosphine (e.g., trimethylphosphine, methyldiphenylphosphine, etc.), substituted or unsubstituted ethylphosphine (e.g., triethylphosphine, ethyldiphenylphosphine, etc.), substituted or unsubstituted propylphosphine, substituted or unsubstituted butylphosphine, substituted or unsubstituted pentylphosphine, substituted or unsubstituted octylphosphine (e.g., trioctylphosphine (TOP)), etc.; phosphine oxides such as substituted or unsubstituted methylphosphine oxide (e.g., trimethylphosphine oxide, methyldiphenylphosphine oxide, etc.), substituted or unsubstituted ethylphosphine oxide (e.g., triethylphosphine oxide, ethyldiphenylphosphine oxide, etc.), substituted or unsubstituted propylphosphine oxide, substituted or unsubstituted butylphosphine oxide, substituted or unsubstituted octylphosphine oxide (e.g., trioctylphosphine oxide (TOPO)), etc.; diphenylphosphine, triphenylphosphine or their oxide compounds; C5-C20 alkyl phosphinic acids such as hexylphosphinic acid, octylphosphinic acid, dodecylphosphinic acid, tetradecylphosphinic acid, hexadecylphosphinic acid, or octadecylphosphinic acid; C5-C20 alkyl phosphonic acids, etc., but the embodiments are not limited thereto. The organic ligands can be used alone or as a combination of two or more.
[0232] The zinc precursor can be Zn metal powder, ZnO, alkylated Zn compounds (e.g., C2-C30 dialkyl zinc such as diethyl zinc), Zn alkoxides (e.g., zinc ethoxide), Zn carboxylates (e.g., zinc acetate), Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetonate, Zn halides (e.g., Zn chloride), Zn cyanide, Zn hydroxide, Zn carbonate, Zn peroxide or a combination thereof. Examples of the zinc precursor can be dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate or a combination thereof.
[0233] The selenium precursor can include selenium-trioctylphosphine (“Se-TOP”), selenium-tributylphosphine (“Se-TBP”), selenium-triphenylphosphine (“Se-TPP”), selenium-diphenylphosphine (“Se-DPP”) or a combination thereof, but is not limited thereto.
[0234] The tellurium precursor can include tellurium-tributylphosphine (“Te-TBP”), tellurium-triphenylphosphine (“Te-TPP”), tellurium-diphenylphosphine (“Te-DPP”) or a combination thereof, but is not limited thereto.
[0235] The sulfur precursor can be hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, mercaptopropylsilane, sulfur-trioctylphosphine (“S-TOP”), sulfur-tributylphosphine (“S-TBP”), sulfur-triphenylphosphine (“S-TPP”), sulfur-trioctylamine (“S-TOA”), bis(trialkylsilyl)sulfide, bis(trialkylsilylalkyl)sulfide (e.g., bis(trimethylsilylmethyl)sulfide), ammonium sulfide, sodium sulfide, or a combination thereof.
[0236] Particles comprising the first semiconductor nanocrystal and optionally the second semiconductor nanocrystal can be separated and washed in the manner described herein before undergoing subsequent reactions (e.g., reactions for forming a semiconductor nanocrystal shell containing zinc and sulfur). The separated and washed particles can be dispersed in a suitable organic solvent (e.g., an aromatic solvent such as toluene or an aliphatic hydrocarbon solvent such as octane) and added to the subsequent reaction.
[0237] In an embodiment, a method for manufacturing semiconductor nanoparticles can include: contacting (e.g., reacting) a zinc precursor (e.g., zinc carboxylate) and a sulfur precursor in a reaction medium containing an organic solvent in the presence of particles comprising the first semiconductor nanocrystal and optionally the second semiconductor nanocrystal; and adding a metal halide to the reaction medium.
[0238] A shell layer containing zinc and sulfur can be formed on the particles by the reaction. The zinc precursor (zinc carboxylate) can include: a first zinc precursor (e.g., a first zinc carboxylate) comprising a first organic ligand and a zinc ion and a second zinc precursor (e.g., a second zinc carboxylate) comprising a second organic ligand and a zinc ion. Details of the first organic ligand, the second organic ligand, the organic solvent, and the sulfur precursor are as described herein. The sulfur precursor for forming the ZnS shell layer is as described herein. In an embodiment, the sulfur precursor can include a thiol compound (e.g., a monothiol compound having an alkyl group of C1-C30, C5-C24, or C8-C12, e.g., dodecanethiol).
[0239] In semiconductor nanocrystal shells, conventional synthesis methods for providing a zinc sulfide-based shell (e.g., the outermost shell) use zinc carboxylates (e.g., zinc oleate) having relatively long organic chains. The present inventors have found that such long-chain zinc carboxylates have a relatively slow reaction rate, making it difficult to provide a ZnS shell of desired quality (uniformity). Additionally, the long-chain carboxylate (carboxylate salt) derived from the zinc precursor can be included as a long-chain ligand on the surface of the resulting semiconductor nanoparticles, which may not have an adverse effect on the luminescence efficiency in solution state or in photoluminescence-type devices, but can act as an insulator in an electroluminescent device to hinder charge injection and cause device performance degradation. To reduce the organic content, surface modification of the semiconductor nanoparticles with metal halides (e.g., zinc chloride) can be considered. However, the present inventors have found that the resulting semiconductor nanoparticles obtained by such modification may not exhibit the desired level of dispersion in organic solvents, and thus there are still technical difficulties in forming the luminescent layer of an electroluminescent device via a solution process.
[0240] Surprisingly, the present inventors have found that semiconductor nanoparticles manufactured by the method described herein can exhibit the desired dispersion for a subsequent luminescent layer formation process in forming a shell layer including zinc and sulfur, and a luminescent layer including the semiconductor nanoparticles can contribute to improved properties and extended lifetime of the resulting electroluminescent device.
[0241] Without wishing to be bound by any theory, a zinc precursor having a long-chain carboxylate (carboxylate salt) (e.g., the second zinc precursor) may show a significant difference in pKa compared to the first zinc precursor, and the combination of these zinc precursors can contribute to the uniform growth of a zinc sulfide (ZnS) shell layer. Additionally, it is believed that the combination can optimize the total organic content of the ligand system disposed in the outermost layer of the semiconductor nanoparticles, thereby enabling improved properties during the operation of an electroluminescent device and effectively preventing device degradation to achieve an extended lifetime.
[0242] The first zinc precursor may include a first organic ligand and a zinc ion, which can be obtained by a reaction between a carboxylic acid corresponding to the first organic ligand (hereinafter, the first carboxylic acid) and a suitable zinc compound (e.g., zinc acetate). The second zinc precursor may include a second organic ligand and a zinc ion, which can be obtained by a reaction between a carboxylic acid corresponding to the second organic ligand (hereinafter, the second carboxylic acid) and a suitable zinc compound (e.g., zinc acetate). Suitable zinc compounds may include the zinc precursors described herein (e.g., for the synthesis of the core and the formation of a ZnSe shell layer). Details of the first organic ligand and the second organic ligand are as described herein.
[0243] The first carboxylic acid is a carboxylic acid containing the first organic ligand. In an embodiment, the first carboxylic acid may be represented by Chemical Formula 2:
[0244] Chemical Formula 2
[0245]
[0246] Where the definitions of R and n are the same as those in Chemical Formula 1.
[0247] The first carboxylic acid may have a pKa greater than or equal to about 4.8, greater than or equal to about 4.9, greater than or equal to about 5.5, greater than or equal to about 5.8, greater than or equal to about 6.5, or greater than or equal to about 7. The first carboxylic acid may have a pKa lower than the pKa of the second carboxylic acid. In an embodiment, the first carboxylic acid may have a pKa less than or equal to about 9, less than or equal to about 8.8, less than or equal to about 8.3, less than or equal to about 7.5, less than or equal to about 6.7, less than or equal to about 5.8, or less than or equal to about 4.9.
[0248] The first carboxylic acid may include propionic acid, valeric acid, caproic acid, caprylic acid, ethylhexanoic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, ethyl butyric acid, propyl valeric acid, methyl butyric acid, butyl octanoic acid, or a combination thereof.
[0249] The second carboxylic acid is a carboxylic acid containing the second organic ligand as described above. In an embodiment, the second organic ligand may include linolenic acid, linoleic acid, oleic acid, elaidic acid, stearic acid, myristic acid, palmitic acid, or a combination thereof.
[0250] The second carboxylic acid may have a pKa greater than or equal to about 8.9, greater than or equal to about 9, greater than or equal to about 9.1, greater than or equal to about 9.8, greater than or equal to about 10, greater than or equal to about 10.1, or greater than or equal to about 10.14.
[0251] In an embodiment, the first zinc precursor may have the following structure, but is not limited thereto:
[0252]
[0253]
[0254] .
[0255] In an embodiment, the second zinc precursor may have the following structure, but is not limited thereto:
[0256] .
[0257] The metal halide may include zinc halide, aluminum halide, or a combination thereof. The zinc halide may include zinc chloride, zinc fluoride, zinc bromide, zinc iodide, or a combination thereof. The aluminum halide may include aluminum chloride, aluminum bromide, aluminum fluoride, aluminum iodide, or a combination thereof.
[0258] In an embodiment, a reaction medium containing an organic solvent and optionally an organic ligand can be vacuum-treated. The organic ligand is as described herein. The vacuum treatment can include heating (or vacuum-treating) the solvent and optionally the ligand compound to a predetermined temperature (e.g., greater than or equal to about 100 °C) under vacuum. The vacuum-treated reaction medium can be replaced with an inert gas atmosphere and heated again to a predetermined temperature (e.g., greater than or equal to about 120 °C or the reaction temperature).
[0259] In an embodiment, particles and a sulfur precursor can be added to the reaction medium heated to a predetermined temperature. In an embodiment, a first zinc precursor can be added to the reaction medium (one, two, or more than two times) and contacted with the sulfur precursor, and then a second zinc precursor can be added to the reaction medium and contacted with the sulfur precursor. In an embodiment, the second zinc precursor can be added to the reaction medium (one, two, or more than two times) and first contacted with the sulfur precursor, and then the first zinc precursor can be added to the reaction medium and contacted with the sulfur precursor.
[0260] The first zinc precursor can be added to the reaction medium more than once (e.g., two or more times) in predetermined aliquots. The second zinc precursor can be added to the reaction medium more than once (e.g., two or more times) in predetermined aliquots.
[0261] In an embodiment, after the first zinc precursor (or the second zinc precursor) contacts the sulfur precursor, a metal halide can be added to the reaction medium.
[0262] In an embodiment, the first zinc precursor can first contact the sulfur precursor, and then the second zinc precursor can contact the sulfur precursor. The second zinc precursor can be added to the reaction medium before, simultaneously with, or after adding the metal halide. In an embodiment, the second zinc precursor can first contact the sulfur precursor, and then the first zinc precursor can contact the sulfur precursor. The first zinc precursor can be added to the reaction medium before, simultaneously with, or after adding the metal halide.
[0263] In an embodiment, relative to 1 mole of the first zinc precursor, the amount of the second zinc precursor can be greater than or equal to about 0.01 mole, greater than or equal to about 0.03 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.07 mole, greater than or equal to about 0.09 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.2 mole, greater than or equal to about 0.3 mole, greater than or equal to about 0.4 mole, greater than or equal to about 0.5 mole, greater than or equal to about 0.6 mole, greater than or equal to about 0.7 mole, greater than or equal to about 0.8 mole, greater than or equal to about 0.9 mole, greater than or equal to about 1 mole, greater than or equal to about 1.2 moles, greater than or equal to about 1.5 moles, greater than or equal to about 1.7 moles, greater than or equal to about 1.9 moles, greater than or equal to about 2 moles, greater than or equal to about 2.1 moles, greater than or equal to about 2.3 moles, greater than or equal to about 2.5 moles, greater than or equal to about 2.7 moles, greater than or equal to about 2.9 moles, greater than or equal to about 3 moles, greater than or equal to about 3.5 moles, greater than or equal to about 4 moles, greater than or equal to about 4.5 moles, greater than or equal to about 5 moles, greater than or equal to about 5.5 moles, greater than or equal to about 6 moles, greater than or equal to about 6.5 moles, greater than or equal to about 7 moles, greater than or equal to about 7.5 moles, greater than or equal to about 8 moles, greater than or equal to about 8.5 moles, greater than or equal to about 9 moles, greater than or equal to about 9.5 moles, greater than or equal to about 10 moles, greater than or equal to about 50 moles, or greater than or equal to about 100 moles.
[0264] In an embodiment, relative to 1 mole of the first zinc precursor, the amount of the second zinc precursor can be less than or equal to about 100 moles, less than or equal to about 90 moles, less than or equal to about 80 moles, less than or equal to about 70 moles, less than or equal to about 60 moles, less than or equal to about 50 moles, less than or equal to about 40 moles, less than or equal to about 30 moles, less than or equal to about 20 moles, less than or equal to about 10 moles, less than or equal to about 9 moles, less than or equal to about 8 moles, less than or equal to about 7 moles, less than or equal to about 6 moles, less than or equal to about 5 moles, less than or equal to about 4 moles, less than or equal to about 3 moles, less than or equal to about 2 moles, less than or equal to about 1 mole, less than or equal to about 0.8 moles, less than or equal to about 0.6 moles, less than or equal to about 0.4 moles, less than or equal to about 0.3 moles, less than or equal to about 0.2 moles, less than or equal to about 0.06 moles, or less than or equal to about 0.03 moles.
[0265] In an embodiment, relative to 1 mole of the total zinc precursor (i.e., the sum of the first zinc precursor and the second zinc precursor), the amount of the metal halide can be greater than or equal to about 0.01 mole, greater than or equal to about 0.03 mole, greater than or equal to about 0.04 mole, greater than or equal to about 0.05 mole, greater than or equal to about 0.07 mole, greater than or equal to about 0.09 mole, greater than or equal to about 0.1 mole, greater than or equal to about 0.12 mole, greater than or equal to about 0.14 mole, greater than or equal to about 0.16 mole, greater than or equal to about 0.18 mole, greater than or equal to about 0.2 mole, greater than or equal to about 0.21 mole, greater than or equal to about 0.23 mole, greater than or equal to about 0.25 mole, greater than or equal to about 0.27 mole, greater than or equal to about 0.29 mole, greater than or equal to about 0.3 mole, greater than or equal to about 0.35 mole, greater than or equal to about 0.4 mole, greater than or equal to about 0.45 mole, greater than or equal to about 0.5 mole, greater than or equal to about 0.55 mole, greater than or equal to about 0.6 mole, greater than or equal to about 0.65 mole, greater than or equal to about 0.7 mole, greater than or equal to about 0.75 mole, greater than or equal to about 0.8 mole, greater than or equal to about 0.85 mole, greater than or equal to about 0.9 mole, greater than or equal to about 0.95 mole, greater than or equal to about 1 mole, greater than or equal to about 5 moles, greater than or equal to about 10 moles, greater than or equal to about 50 moles, or greater than or equal to about 100 moles.
[0266] In an embodiment, relative to 1 mole of the total zinc precursor, the amount of the metal halide can be less than or equal to about 100 moles, less than or equal to about 90 moles, less than or equal to about 80 moles, less than or equal to about 70 moles, less than or equal to about 40 moles, less than or equal to about 10 moles, less than or equal to about 3 moles, less than or equal to about 1 mole, less than or equal to about 0.96 mole, less than or equal to about 0.84 mole, less than or equal to about 0.72 mole, less than or equal to about 0.63 mole, less than or equal to about 0.58 mole, less than or equal to about 0.52 mole, less than or equal to about 0.49 mole, less than or equal to about 0.43 mole, less than or equal to about 0.41 mole, less than or equal to about 0.4 mole, less than or equal to about 0.38 mole, less than or equal to about 0.34 mole, less than or equal to about 0.28 mole, less than or equal to about 0.26 mole, less than or equal to about 0.24 mole, less than or equal to about 0.22 mole, less than or equal to about 0.2 mole, less than or equal to about 0.19 mole, less than or equal to about 0.17 mole, less than or equal to about 0.15 mole, less than or equal to about 0.13 mole, less than or equal to about 0.11 mole, less than or equal to about 0.08 mole, less than or equal to about 0.06 mole, or less than or equal to about 0.03 mole.
[0267] A predetermined temperature or reaction temperature can be appropriately selected. In an embodiment, the vacuum-treated reaction medium can be heated to a first temperature, and a first semiconductor nanocrystal, a first zinc precursor (or a second zinc precursor), and a sulfur precursor can be added, and then the reaction medium can be raised to the reaction temperature. The first temperature can be lower than the reaction temperature. The difference between the first temperature and the reaction temperature can be in the range of about 80 °C to about 250 °C, about 80 °C to about 200 °C, about 120 °C to about 180 °C, about 140 °C to about 160 °C, or a combination thereof.
[0268] The reaction temperature can be greater than or equal to about 250 °C, greater than or equal to about 260 °C, greater than or equal to about 270 °C, greater than or equal to about 280 °C, greater than or equal to about 300 °C, greater than or equal to about 320 °C, greater than or equal to about 340 °C, or greater than or equal to about 350 °C. The reaction temperature can be less than or equal to about 400 °C, less than or equal to about 390 °C, less than or equal to about 380 °C, less than or equal to about 370 °C, less than or equal to about 360 °C, less than or equal to about 350 °C, less than or equal to about 345 °C, less than or equal to about 340 °C, less than or equal to about 330 °C, less than or equal to about 320 °C, less than or equal to about 310 °C, less than or equal to about 290 °C, less than or equal to about 280 °C, less than or equal to about 270 °C, or less than or equal to about 250 °C. In an embodiment, the reaction temperature can vary in the range of about 340 °C to about 250 °C.
[0269] The reaction time can be appropriately selected considering the types of precursors, the reaction temperature, the desired thickness of the ZnS shell in the final semiconductor nanoparticles, etc. The reaction time can be greater than or equal to about 10 minutes, greater than or equal to about 15 minutes, greater than or equal to about 20 minutes, greater than or equal to about 25 minutes, greater than or equal to about 30 minutes, greater than or equal to about 35 minutes, or greater than or equal to about 40 minutes. The reaction time can be less than or equal to about 3 hours, less than or equal to about 2 hours, less than or equal to about 200 minutes, less than or equal to about 180 minutes, less than or equal to about 160 minutes, less than or equal to about 140 minutes, less than or equal to about 120 minutes, less than or equal to about 100 minutes, less than or equal to about 90 minutes, or less than or equal to about 80 minutes.
[0270] After the reaction is completed, the particles including the first semiconductor nanocrystal or the second semiconductor nanocrystal, or the obtained semiconductor nanoparticles can be collected as follows: pouring an excess of non-solvent to remove the excess organic material uncoordinated on the surface, and then centrifuging the resulting mixture. For example, after the reaction is completed, adding a non-solvent to the reaction product can separate the semiconductor nanoparticles coordinated with the ligand compound. The non-solvent can be a polar solvent that is miscible with the solvent used in the core formation and / or shell formation reaction but cannot disperse the fabricated nanocrystals. The non-solvent can be determined according to the solvent used in the reaction and can include, for example, acetone, ethanol, butanol, isopropanol, water, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), diethyl ether, formaldehyde, acetaldehyde, ethylene glycol, solvents having solubility parameters similar to those of the non-solvents listed above, or a combination thereof, but not limited thereto. Separation can be carried out by centrifugation, precipitation, chromatography or distillation. The separated nanocrystals can be washed by adding them to a washing solvent as needed. The washing solvent is not particularly limited and can be a solvent having solubility parameters similar to those of the ligand, and examples thereof include hexane, heptane, octane, chloroform, toluene, benzene, etc.
[0271] The semiconductor nanoparticles of the embodiment may not be dispersible in water, any of the non-solvents listed above, or a mixture thereof. The semiconductor nanoparticles of the embodiment may be water-insoluble. The semiconductor nanoparticles of the embodiment may be dispersible in the aforementioned organic solvents. In an embodiment, the semiconductor nanoparticles may be dispersible in a C6-C40 aliphatic hydrocarbon, a C6-C40 aromatic hydrocarbon, or a mixture thereof.
[0272] The obtained semiconductor nanoparticles may exhibit the properties described herein.
[0273] In an embodiment, the semiconductor nanoparticles can form a composition (ink) for an inkjet printing process and can provide a light-emitting layer pattern through the inkjet printing process. The composition for the inkjet process can include the semiconductor nanoparticles of the embodiment and a liquid carrier. The semiconductor nanoparticles of the embodiment can form a colloidal dispersion in the liquid carrier. At least a part of the liquid carrier can be removed from the light-emitting layer after the inkjet process. The liquid carrier can include an organic solvent. The organic solvent can include the dispersion solvents described herein. The organic solvent can be an organic solvent having a relatively high boiling point at atmospheric pressure or ambient pressure. The boiling point of the organic solvent or the liquid carrier can be greater than or equal to about 120 °C, greater than or equal to about 130 °C, greater than or equal to about 140 °C, greater than or equal to about 150 °C, greater than or equal to about 160 °C, greater than or equal to about 170 °C, or greater than or equal to about 180 °C. The boiling point of the organic solvent can be less than or equal to about 300 °C, less than or equal to about 280 °C, less than or equal to about 270 °C, less than or equal to about 250 °C, or less than or equal to about 200 °C. The organic solvent can include a substituted or unsubstituted aromatic solvent such as cyclohexylbenzene, a substituted or unsubstituted C6-C15 aliphatic hydrocarbon solvent such as hexane, octane, or decane, or a combination thereof. In the case of using a mixed solvent, the mixing ratio can be adjusted in consideration of the conditions for the inkjet process (e.g., boiling point, viscosity). For example, when using a mixed solvent of an aromatic solvent and an aliphatic solvent, the ratio can be adjusted to 1:0.1 to 1:10, 1:0.3 to 1:3, or 1:0.5 to 1:2 (volume: volume), but is not limited thereto.
[0274] The semiconductor nanoparticles can be included in the ink composition by having the properties described herein, contributing to the composition exhibiting an appropriate viscosity. The viscosity can be in the range of about 0.5 centipoise (cPs) to about 30 cPs, about 1 cPs to about 15 cPs, about 1.5 cPs to about 10 cPs, about 2 cPs to about 8 cPs, about 2.5 cPs to about 5 cPs, about 2.8 cPs to about 3.5 cPs, or a combination thereof.
[0275] The composition for inkjet printing can exhibit surface tension or wettability with respect to a common layer (e.g., a hole-assisted layer or an electron-assisted layer). The surface tension can be in the range of about 10 millinewtons per meter (mN / m) to about 100 mN / m, about 15 mN / m to about 80 mN / m, about 20 mN / m to about 50 mN / m, about 25 mN / m to about 45 mN / m, about 30 mN / m to about 40 mN / m, about 33 mN / m to about 38 mN / m, or a combination thereof.
[0276] Forming the light-emitting layer by an inkjet printing method may include: putting or accommodating an ink composition containing the semiconductor nanoparticles in a device equipped with an inkjet printing nozzle, and ejecting / depositing droplets of the composition from the nozzle to a desired position (e.g., the surface of a hole transport layer or an electron transport layer defined by a partition wall or a dam such as a pixel defining layer (PDL)). (See Figure 4 and Figure 5 )
[0277] In the electroluminescent device of an embodiment, the thickness of the light-emitting layer can be appropriately selected. In an embodiment, the light-emitting layer 3 or 30 may include a single layer of semiconductor nanoparticles. In an embodiment, the light-emitting layer 3 or 30 may include a single layer of semiconductor nanoparticles, such as a single layer of one or more, two or more, three or more, or four or more and 20 or less, 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less semiconductor nanoparticles. The light-emitting layer 3 or 30 may have a thickness greater than or equal to about 5 nm, such as greater than or equal to about 10 nm, greater than or equal to about 20 nm, or greater than or equal to about 30 nm and less than or equal to about 200 nm, such as less than or equal to about 150 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, or less than or equal to about 50 nm. The light-emitting layer 3 or 30 may have a thickness of, for example, about 10 nm to about 150 nm, about 20 nm to about 100 nm, about 30 nm to about 50 nm, or a combination thereof.
[0278] The formation of the light-emitting layer can be carried out as follows: preparing a composition including nanostructures (configured to emit desired light), and applying or depositing the composition on a substrate (e.g., including an electrode or a charge assisting layer) by an appropriate method, such as by an appropriate method (e.g., spin coating, inkjet printing, etc.).
[0279] The formation of the light-emitting layer may further include heat-treating the coated or deposited layer of semiconductor nanoparticles. The heat-treatment (e.g., thermal treatment or heat treatment) temperature is not particularly limited, and it can be appropriately selected considering the boiling point of the organic solvent. For example, the heat-treatment temperature may be greater than or equal to about 60 °C, or greater than or equal to about 70 °C and less than or equal to about 250 °C, or less than or equal to about 180 °C. The type of the organic solvent for the coating solution is not particularly limited, and it can be appropriately selected. In an embodiment, the organic solvent may include a substituted or unsubstituted aliphatic hydrocarbon organic solvent, a substituted or unsubstituted aromatic hydrocarbon solvent, a substituted or unsubstituted alicyclic hydrocarbon solvent, an acetate solvent, or a combination thereof.
[0280] In an embodiment, the light-emitting layer can be a single layer or a multi-layer structure having at least two layers. In the multi-layer structure, adjacent layers (e.g., the first light-emitting layer and the second light-emitting layer) can be configured to emit first light (e.g., green light, blue light, or red light). In the multi-layer structure, adjacent layers (e.g., the first light-emitting layer and the second light-emitting layer) can have the same or different compositions, ligands, or combinations thereof. In an embodiment, the (multi-layer) light-emitting layer can have a varying (increasing or decreasing) amount of halogen in the thickness direction. In an embodiment, in the (multi-layer) light-emitting layer, the amount of halogen can increase in the direction towards the electron assisting layer. In the (multi-layer) light-emitting layer, the amount or content of the organic ligand can decrease in the direction towards the electron assisting layer. In the (multi-layer) light-emitting layer, the amount or content of the organic ligand can increase in the direction towards the electron assisting layer.
[0281] The electroluminescent device can further include a charge (hole or electron) assisting layer between the first electrode and the second electrode (e.g., anode and cathode). In an embodiment, the electroluminescent device can include a hole assisting layer 20 or an electron assisting layer 40 between the anode 10 and the light-emitting layer 30, between the cathode 50 and the light-emitting layer 30, or a combination thereof. (See Figure 2 and 3 .)
[0282] The light-emitting device according to an embodiment can further include a hole assisting layer. The hole assisting layer 20 can be disposed between the first electrode 10 and the light-emitting layer 30. The hole assisting layer 20 can include a hole injection layer, a hole transport layer, an electron blocking layer, or a combination thereof. The hole assisting layer 20 can be a single-component layer or a multi-layer structure in which adjacent layers include different components.
[0283] The hole assisting layer 20 can have a HOMO energy level such that it can match the HOMO energy level of the light-emitting layer 30 to enhance the mobility of holes transferred from the hole assisting layer 20 to the light-emitting layer 30. In an embodiment, the hole assisting layer 20 can include a hole injection layer close to the first electrode 10 and a hole transport layer close to the light-emitting layer 30.
[0284] The material included in the hole auxiliary layer 20 (e.g., hole transport layer, hole injection layer, or electron blocking layer) is not particularly limited and may include, for example, poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)-diphenylamine) (“TFB”), polyarylamine (polyarylamine), poly(N-vinylcarbazole), poly(3,4-ethylenedioxythiophene) (“PEDOT”), poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (“PEDOT:PSS”), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (“TPD”), 4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl (“α-NPD”), 4,4',4''-tris[phenyl(m-tolyl)amino]triphenylamine (“m-MTDATA”), 4,4',4''-tris(N-carbazolyl)-triphenylamine (“TCTA”), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (“TAPC”), p-type metal oxides (e.g., NiO, WO3, MoO3, etc.), carbon-based materials such as graphene oxide, or a combination thereof, but not limited thereto.
[0285] In the hole auxiliary layer, the thickness of each layer can be appropriately selected. For example, the thickness of each layer can be greater than or equal to about 5 nm, greater than or equal to about 10 nm, greater than or equal to about 15 nm, or greater than or equal to about 20 nm and less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, or less than or equal to about 30 nm, but not limited thereto.
[0286] The electron auxiliary layer 40 can be disposed between the light-emitting layer 30 and the second electrode 50. The electron auxiliary layer 40 can include, for example, an electron injection layer, an electron transport layer, a hole blocking layer, or a combination thereof. The electron auxiliary layer can include, for example, an electron injection layer (“EIL”) that promotes the injection of electrons, an electron transport layer (“ETL”) that promotes the transport of electrons, a hole blocking layer (“HBL”) that blocks the movement of holes, or a combination thereof.
[0287] In an embodiment, the electron injection layer can be disposed between the electron transport layer and the cathode. For example, the hole blocking layer can be disposed between the light-emitting layer and the electron transport (injection) layer, but not limited thereto. The thickness of each layer can be appropriately selected. For example, the thickness of each layer can be greater than or equal to about 1 nm and less than or equal to about 500 nm, but not limited thereto. The electron injection layer can be an organic layer formed by vapor deposition. The electron transport layer can include inorganic oxide nanoparticles or can be an organic layer formed by vapor deposition.
[0288] The electron transport layer (“ETL”), electron injection layer, hole blocking layer, or a combination thereof may include, for example, 1,4,5,8-naphthalenetetracarboxylic dianhydride (“NTCDA”), bathocuproine (“BCP”), tris[3-(3-pyridyl)-mesityl]borane (“3TPYMB”), LiF, tris(8-hydroxyquinoline)aluminum (“Alq3”), tris(8-hydroxyquinoline)gallium (“Gaq3”), tris(8-hydroxyquinoline)indium (“Inq3”), bis(8-hydroxyquinoline)zinc (“Znq2”), bis[2-(2-hydroxyphenyl)benzothiazole]zinc (“Zn(BTZ)2”), bis(10-hydroxybenzo[h]quinoline)beryllium (“BeBq2”), 8-(4-(4,6-di(naphthalen-2-yl)-1,3,5-triazin-2-yl)phenyl)quinolone (“ET204”), lithium 8-hydroxyquinolate (“Liq”), n-type metal oxides (such as ZnO, HfO2, etc.) or a combination thereof, but not limited thereto.
[0289] The electron assisting layer 40 may include an electron transport layer. The electron transport layer may include a plurality of nanoparticles. The plurality of nanoparticles may include a zinc-containing metal oxide.
[0290] The metal oxide may include zinc oxide, magnesium zinc oxide or a combination thereof. The metal oxide may include Zn 1- x M x O, where M is Mg, Ca, Zr, W, Li, Ti, Y, Al or a combination thereof, and 0 ≤ x ≤ 0.5. In an embodiment, in the formula Zn 1-x M x O, M may be magnesium (Mg). In an embodiment, in the formula Zn 1-x M x O, x may be greater than or equal to about 0.01 and less than or equal to about 0.3, such as less than or equal to about 0.25, less than or equal to about 0.2, or less than or equal to about 0.15.
[0291] The absolute value of the LUMO of the aforementioned nanostructures included in the light emitting layer may be greater than or less than the absolute value of the LUMO of the metal oxide. The average size of the nanoparticles may be greater than or equal to about 1 nm, such as greater than or equal to about 1.5 nm, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, or greater than or equal to about 3 nm and less than or equal to about 10 nm, less than or equal to about 9 nm, less than or equal to about 8 nm, less than or equal to about 7 nm, less than or equal to about 6 nm, or less than or equal to about 5 nm.
[0292] In an embodiment, the respective thicknesses of the electron assisting layer 40 (e.g., an electron injection layer, an electron transport layer, or a hole blocking layer) may be greater than or equal to about 5 nm, greater than or equal to about 6 nm, greater than or equal to about 7 nm, greater than or equal to about 8 nm, greater than or equal to about 9 nm, greater than or equal to about 10 nm, greater than or equal to about 11 nm, greater than or equal to about 12 nm, greater than or equal to about 13 nm, greater than or equal to about 14 nm, greater than or equal to about 15 nm, greater than or equal to about 16 nm, greater than or equal to about 17 nm, greater than or equal to about 18 nm, greater than or equal to about 19 nm, or greater than or equal to about 20 nm and less than or equal to about 120 nm, less than or equal to about 110 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, or less than or equal to about 25 nm, but is not limited thereto.
[0293] The device according to an embodiment may have a normal structure. In an embodiment, in the device, the anode 10 disposed on the transparent substrate 100 may include a metal oxide-based transparent electrode (e.g., an ITO electrode), and the cathode 50 facing the anode 10 may include a conductive metal (e.g., having a relatively low work function, such as Mg, Al, etc.). A hole assisting layer 20 (e.g., a hole injection layer such as PEDOT:PSS, a p-type metal oxide, or a combination thereof; a hole transport layer such as TFB, polyvinylcarbazole (“PVK”), or a combination thereof; or a combination thereof) may be provided between the transparent electrode 10 and the light-emitting layer 30. The hole injection layer may be disposed close to the transparent electrode, and the hole transport layer may be disposed close to the light-emitting layer. An electron assisting layer 40 such as an electron injection / transport layer may be disposed between the light-emitting layer 30 and the cathode 50. (See Figure 2 .
[0294] The device according to an embodiment may have an inverted structure. Here, the cathode 50 disposed on the transparent substrate 100 may include a metal oxide-based transparent electrode (e.g., ITO), and the anode 10 facing the cathode may include a metal (e.g., having a relatively high work function, such as Au, Ag, etc.). For example, (optionally doped) n-type metal oxides (crystalline Zn metal oxides, etc.) may be provided as the electron assisting layer 40 (e.g., an electron transport layer) between the transparent electrode 50 and the light-emitting layer 30, and a hole assisting layer 20 (e.g., a hole transport layer including TFB, PVK, or a combination thereof; a hole injection layer including MoO3 or other p-type metal oxides; or a combination thereof) may be disposed between the metal anode 10 and the light-emitting layer 30. (See Figure 3 .
[0295] The aforementioned device can be fabricated by appropriate methods. For example, an electroluminescent device can be fabricated by optionally forming a hole auxiliary layer (e.g., by deposition or coating) on a substrate on which an electrode is provided, forming a light-emitting layer including a nanostructure (e.g., a pattern of the aforementioned nanostructure), and forming an electrode (e.g., by vapor deposition or coating) on the light-emitting layer (optionally, an electron auxiliary layer). The methods for forming the electrode / hole auxiliary layer / electron auxiliary layer can be appropriately selected and are not particularly limited.
[0296] In an embodiment, each layer included in the hole transport region, the light-emitting layer, and each layer included in the electron transport region can be formed in a predetermined region using various methods such as vacuum deposition, spin coating, casting, Langmuir-Blodgett (LB) method, inkjet printing, laser printing, and laser-induced thermal imaging (LITI). For example, the light-emitting layer can be formed by inkjet printing. The inkjet process is as described herein.
[0297] When each layer included in the hole transport region, the light-emitting layer, and each layer included in the electron transport region are formed by vacuum deposition, the deposition conditions can be appropriately selected. For example, the deposition temperature can be from about 100 °C to about 500 °C, the vacuum degree can be from about 10 -8 to about 10 -3 Torr, and the deposition rate range can be from about 0.01 to about 100 Å / sec. The deposition conditions can be selected considering the materials included in the layer to be formed and the structure of the layer to be formed.
[0298] The electroluminescent device can be configured to emit blue light. The wavelength range of blue light is as described herein. The electroluminescent device can be configured to emit green light. The wavelength range of green light is as described herein. The electroluminescent device can be configured to emit red light. The wavelength range of red light is as described herein.
[0299] In the electroluminescent device of an embodiment, the maximum external quantum efficiency (“EQE”) can be greater than or equal to about 4%, greater than or equal to about 5%, greater than or equal to about 6%, greater than or equal to about 7%, greater than or equal to about 8%, greater than or equal to about 9%, greater than or equal to about 10%, greater than or equal to about 10.5%, greater than or equal to about 11%, greater than or equal to about 11.5%, greater than or equal to about 12%, greater than or equal to about 12.5%, greater than or equal to about 13%, greater than or equal to about 13.5%, or greater than or equal to about 14%. In the electroluminescent device of an embodiment, the maximum external quantum efficiency (“EQE”) can be less than or equal to about 50%, less than or equal to about 40%, less than or equal to about 30%, or less than or equal to about 20%.
[0300] The electroluminescent device may have a maximum brightness greater than or equal to about 40,000 nits (cd / m 2 ), greater than or equal to about 50,000 nits, greater than or equal to about 60,000 nits, greater than or equal to about 70,000 nits, greater than or equal to about 80,000 nits, greater than or equal to about 90,000 nits, greater than or equal to about 95,000 nits, greater than or equal to about 100,000 nits, greater than or equal to about 105,000 nits, greater than or equal to about 110,000 nits, greater than or equal to about 115,000 nits, greater than or equal to about 120,000 nits, or greater than or equal to about 125,000 nits. The maximum brightness may be in the range of about 3,000 nits to about 500,000 nits.
[0301] The electroluminescent device may exhibit an improved lifespan. In an embodiment, the lifespan of the electroluminescent device may be measured when driven at a predetermined initial brightness (e.g., 146 nits or 650 nits).
[0302] The lifespan T50 of the electroluminescent device may be greater than or equal to about 10 hours, greater than or equal to about 50 hours, greater than or equal to about 80 hours, greater than or equal to about 100 hours, greater than or equal to about 120 hours, greater than or equal to about 130 hours, greater than or equal to about 150 hours, greater than or equal to about 300 hours, greater than or equal to about 310 hours, greater than or equal to about 350 hours, greater than or equal to about 380 hours, greater than or equal to about 400 hours, greater than or equal to about 450 hours, greater than or equal to about 500 hours, greater than or equal to about 600 hours, greater than or equal to about 700 hours, greater than or equal to about 800 hours, greater than or equal to about 900 hours, greater than or equal to about 1,000 hours, greater than or equal to about 1,500 hours, or longer.
[0303] The lifespan T90 of the electroluminescent device may be greater than or equal to about 10 hours, greater than or equal to about 15 hours, greater than or equal to about 20 hours, greater than or equal to about 25 hours, greater than or equal to about 30 hours, greater than or equal to about 35 hours, greater than or equal to about 40 hours, greater than or equal to about 50 hours, greater than or equal to about 75 hours, greater than or equal to about 100 hours, greater than or equal to about 125 hours, greater than or equal to about 150 hours, greater than or equal to about 175 hours, greater than or equal to about 200 hours, greater than or equal to about 300 hours, greater than or equal to about 310 hours, greater than or equal to about 350 hours, greater than or equal to about 380 hours, greater than or equal to about 400 hours, greater than or equal to about 450 hours, greater than or equal to about 500 hours, greater than or equal to about 600 hours, greater than or equal to about 700 hours, greater than or equal to about 800 hours, greater than or equal to about 900 hours, greater than or equal to about 1,000 hours, greater than or equal to about 1,500 hours, or longer.
[0304] In an embodiment, T50 can be in the range of about 150 hours to about 5,000 hours, about 400 hours to about 4,000 hours, about 500 hours to about 3,500 hours, about 750 hours to about 2,000 hours, about 1,000 hours to about 1,500 hours, or a combination thereof.
[0305] In an embodiment, T90 can be in the range of about 13 hours to about 5,000 hours, about 15 hours to about 2,800 hours, about 18 hours to about 1,200 hours, about 22 hours to about 1,000 hours, about 31 hours to about 800 hours, about 50 hours to about 700 hours, about 60 hours to about 500 hours, about 80 hours to about 400 hours, or a combination thereof.
[0306] In an embodiment, the display device includes the electroluminescent device described herein.
[0307] The display device may include a first pixel and a second pixel configured to emit light different from that of the first pixel.
[0308] The display device (e.g., a display panel) may include a first pixel and a second pixel configured to emit light of a color different from that of the first pixel. In an embodiment, the first light emitted from the light-emitting layer can be extracted through the second electrode (e.g., in the Z direction) (see Figure 4 or Figure 5 ). In an embodiment, the first light can be extracted through the (transparent) first electrode and optionally through the substrate 100 (see Figure 3 ). The light-emitting layer can be disposed within a pixel (or sub-pixel) in the display device (display panel) as described below (see Figure 4 or Figure 5 ).
[0309] Referring to Figure 6 , the display panel 1000 according to an embodiment may include a display area 1000D for displaying an image and a non-display area 1000P provided around the display area 1000D, and the bonding elements may be located in the non-display area 1000P.
[0310] The display area 1000D may include a plurality of pixels PX arranged along rows (e.g., in the x direction) and / or columns (e.g., in the y direction), and each pixel PX may include a plurality of sub-pixels PX1, PX2, and PX3 that display different colors. As an example, a configuration is shown in which three sub-pixels PX1, PX2, and PX3 constitute one pixel PX, but the configuration is not limited thereto. Additional sub-pixels such as white sub-pixels may be further included, and one or more sub-pixels that display the same color may be included. The plurality of pixels PX may be arranged, for example, in a Bayer matrix, a PenTile matrix, and / or a diamond matrix, but is not limited thereto.
[0311] Each of the sub-pixels PX1, PX2, and PX3 may be configured to display the following colors: the primary colors or a combination of the primary colors, for example, red, green, blue, or a combination thereof (e.g., white light). For example, the first sub-pixel PX1 may be configured to display red, the second sub-pixel PX2 may be configured to display green, and the third sub-pixel PX3 may be configured to display blue.
[0312] In the figure, each sub-pixel is depicted as having the same size, but the present disclosure is not limited thereto. For example, at least one of the sub-pixels may be larger or smaller than the other sub-pixels, or may have a different shape from the other sub-pixels.
[0313] In an embodiment, the display panel of the embodiment may include a light-emitting panel, and the light-emitting panel may include a lower substrate 110, a buffer layer 111, thin-film transistors TFTs, and light-emitting elements 180. The display panel may further include circuit elements for switching (changing) and / or driving each of the light-emitting elements.
[0314] Refer to Figure 7 , in the light-emitting panel of the embodiment, a light-emitting element 180 may be provided for each of the sub-pixels PX1, PX2, and PX3. The light-emitting elements 180 provided in each of the sub-pixels PX1, PX2, and PX3 may be independently driven. The sub-pixels may include blue sub-pixels, red sub-pixels, or green sub-pixels. At least one of the light-emitting elements 180 may be an electroluminescent element according to the embodiment described herein.
[0315] Details of the substrate are the same as those described herein. The buffer layer 111 may include an organic material, an inorganic material, or an organic-inorganic material. The buffer layer 111 may include, for example, an oxide, a nitride, or a oxynitride, and may include, for example, silicon oxide, silicon nitride, silicon oxynitride, or a combination thereof, but is not limited thereto. The buffer layer 111 may be one layer, two layers, or more layers, and may cover a part or the entire surface of the lower substrate 110. The buffer layer 111 may be omitted.
[0316] The thin-film transistor TFT can be a three-terminal element for switching and / or driving the light-emitting element 180, and one or two or more of them can be included for each sub-pixel. The thin-film transistor TFT can include a gate electrode 124, a semiconductor layer 154 overlapping the gate electrode 124, a gate insulating layer 140 between the gate electrode 124 and the semiconductor layer 154, and source and drain electrodes 173 and 175 electrically connected to the semiconductor layer 154. A coplanar top-gate structure is shown as an example, but the structure is not limited thereto and can have various structures.
[0317] The gate electrode 124 is electrically connected to a gate line (not shown), and can include, for example, a low-resistance metal such as aluminum (Al), molybdenum (Mo), copper (Cu), titanium (Ti), silver (Ag), gold (Au), its alloy, or a combination thereof, but is not limited thereto.
[0318] The semiconductor layer 154 can be an inorganic semiconductor such as amorphous silicon, polycrystalline silicon, or an oxide semiconductor; an organic semiconductor; an organic-inorganic semiconductor; or a combination thereof. For example, the semiconductor layer 154 can include an oxide semiconductor containing at least one of indium (In), zinc (Zn), tin (Sn), and gallium (Ga), and the oxide semiconductor can include, for example, indium-gallium-zinc oxide, zinc-tin oxide, or a combination thereof, but they are not limited thereto. The semiconductor layer 154 can include a channel region and doping regions disposed on both sides of the channel region and electrically connected to the source electrode 173 and the drain electrode 175, respectively.
[0319] The gate insulating layer 140 can include an organic material, an inorganic material, or an organic-inorganic material, and can include, for example, an oxide, a nitride, or a oxynitride, and can include, for example, silicon oxide, silicon nitride, silicon oxynitride, or a combination thereof, but is not limited thereto. In the drawings, an example in which the gate insulating layer 140 is formed on the entire surface of the lower substrate 110 is shown, but the present disclosure is not limited thereto and can be selectively formed between the gate electrode 124 and the semiconductor 154. The gate insulating layer 140 can be formed of one layer or two or more layers.
[0320] The source electrode 173 and the drain electrode 175 can include, for example, a low-resistance metal such as aluminum (Al), molybdenum (Mo), copper (Cu), titanium (Ti), silver (Ag), gold (Au), its alloy, or a combination thereof, but is not limited thereto. The source electrode 173 and the drain electrode 175 can be electrically connected to the doping regions of the semiconductor layer 154, respectively. The source electrode 173 is electrically connected to a data line (not shown), and the drain electrode 175 is electrically connected to the light-emitting element 180.
[0321] An interlayer insulating layer 145 may be additionally formed between the gate electrode 124 and the source / drain electrodes 173 and 175. The interlayer insulating layer 145 may include an organic material, an inorganic material, or an organic-inorganic material, such as an oxide, a nitride, or a oxynitride, such as silicon oxide, silicon nitride, silicon oxynitride, or a combination thereof, but is not limited thereto. The interlayer insulating layer 145 may be formed of one layer, two layers, or more layers.
[0322] A protective layer 160 may be formed on the thin film transistor TFT. The protective layer 160 may be, for example, a passivation layer. The protective layer 160 may include an organic material, an inorganic material, or an organic-inorganic material, such as polyacrylic acid, polyimide, polyamide, poly(amide-imide), or a combination thereof, but is not limited thereto. The protective layer 160 may be formed of one layer, two layers, three layers, or more layers.
[0323] In an embodiment, one of the first electrodes 1 and 10 and the second electrodes 5 and 50 may be a pixel electrode connected to the TFT, and the other of them may be a common electrode.
[0324] In an embodiment, the light emitting device or the display device including the same may be used in a top emission type, a bottom emission type, a dual emission type, or a combination thereof.
[0325] In an embodiment, the first electrodes 1 and 10 may be a light transmissive electrode and the second electrodes 5 and 50 may be a reflective electrode, and the display panel may be a bottom emission type display panel that emits light toward the first electrode 10 and the lower substrate 110 (if any). In an embodiment, the first electrodes 1 and 10 may be a reflective electrode and the second electrodes 5 and 50 may be a light transmissive electrode, and the display panel may be a top emission type display panel that emits light toward the opposite side of the first electrode 10 and the lower substrate 110 (if any). In an embodiment, both the first electrode and the second electrode may be a semi-transparent electrode, and the display panel 1000 may be a dual emission type display panel that emits light on the substrate side and on the opposite side of the substrate.
[0326] The display device or the electronic device may include (or may be) a device or equipment such as a television, virtual reality / augmented reality (VR / AR), a handheld terminal, a monitor, a laptop computer, an electronic display board, a camera, or a component for an automatic (e.g., autonomous driving) vehicle.
[0327] Specific embodiments are described below. However, the embodiments described below are only for specific illustration or explanation of the present disclosure, and the scope of the present disclosure is not limited thereto.
[0328] Embodiment
[0329] 1. Photoluminescence (PL) analysis and TRPL analysis
[0330] The photoluminescence spectra and absolute QY of the nanoparticles were obtained at room temperature with an excitation wavelength of 372 nm using a Hitachi F-7000 spectrophotometer or a Hamamatsu QY instrument (Quantaurus-QY absolute PL quantum yield spectrophotometer C11347-11).
[0331] 2. GC analysis
[0332] Gas chromatography analysis was performed using an Agilent GC-MS 7890B / 5977A. No standard substance was used. After separating the crude product containing the fabricated semiconductor nanoparticles twice with ethanol (EtOH) and drying under vacuum, 0.1 mg of the fabricated semiconductor nanoparticles was mixed with 1 microliter (μL) of TMAH (tetramethylammonium hydroxide) and placed in a hood for 2 minutes, followed by py-GC / MS measurement.
[0333] Pyrolyzer: 450 °C
[0334] Column: 30 m x 0.25 mm x 0.25 mm (UA5)
[0335] Flow rate: He (1 mL / min)
[0336] Inlet temperature: 300 °C
[0337] Oven temperature: 50 °C (held for 2 minutes), increased to 320 °C at a rate of 20 °C / minute (held for 10 minutes)
[0338] Analyzer: quadrupole (range: 10 to 550 m / z)
[0339] 3. TGA
[0340] Thermogravimetric analysis was performed using a Trios V3.2 system (TA Instruments) from 20 °C to 600 °C at a heating rate of 10 °C / minute under nitrogen. The weight loss from 200 °C to 550 °C was measured as the organic content.
[0341] 4. Electroluminescence measurement
[0342] The current according to the applied voltage was measured using a Keithley 2635B source meter, and the electroluminescence properties (e.g., brightness and EQE) of the light-emitting device were measured using a CS2000 spectrometer.
[0343] 5. Lifetime
[0344] T90 (h): The time (hours) taken for the brightness to reach 90% of the initial brightness when driven at a predetermined brightness (e.g., 650 nits or 146 nits).
[0345] T50(h): The time (hours) it takes for the brightness to reach 50% of the initial brightness when driven at a predetermined brightness (e.g., 650 nits or 146 nits).
[0346] Unless otherwise specified, the following syntheses are carried out under an inert gas atmosphere (e.g., under nitrogen). Unless otherwise specified, the precursor contents are provided as molar contents.
[0347] Reference Example 1: Preparation of Particles Comprising First and Second Semiconductor Nanocrystals
[0348] Selenium (Se), sulfur (S), and tellurium (Te) were dispersed in trioctylphosphine (TOP) to obtain a 2 molar concentration (M) Se / TOP stock solution, a 1 M S / TOP stock solution, and a 0.1 M Te / TOP stock solution.
[0349] In a 300 milliliter (mL) reaction flask containing trioctylamine, 4.5 millimoles (mmol) of zinc acetate and oleic acid were added and heated to 120 °C under vacuum. After 1 hour, the atmosphere inside the reactor was switched to an inert gas.
[0350] After heating to 240 °C to 300 °C, the prepared Se / TOP stock solution and Te / TOP stock solution were rapidly injected at a Te / Se ratio of 1 / 15. The reaction was carried out for 40 minutes. After the reaction was completed, ethanol was added to the reaction solution, which was rapidly cooled to room temperature and centrifuged to obtain ZnTeSe semiconductor nanocrystals. The obtained precipitate was dispersed in hexane to obtain a ZnSeTe core. The average size of the core was approximately 3 nm.
[0351] In a 300 mL reaction flask containing TOA, zinc acetate and oleic acid were added and vacuum-treated at 120 °C. Nitrogen (N2) was allowed to flow into the flask, and then the flask was heated to the reaction temperature (340 °C). The hexane dispersion of the ZnSeTe core was rapidly added to the reaction flask, and then the Se / TOP stock solution was added to carry out the reaction. Regarding the formation of the ZnSe shell, the amount of the selenium precursor was 0.67 moles relative to 1 mole of the zinc precursor.
[0352] After the reaction was completed, the reactor was cooled to room temperature, and ethanol was added to the reaction solution to precipitate nanoparticles containing the first semiconductor nanocrystals (ZnTeSe) and the second semiconductor nanocrystals (ZnSe). The precipitate was collected by centrifugation, and it was confirmed that the obtained nanoparticles were dispersible in a hydrocarbon solvent such as octane.
[0353] Reference Example 2: Synthesis of ZnMgO Nanoparticles
[0354] Zinc acetate dihydrate and magnesium acetate tetrahydrate were added to a reactor containing dimethyl sulfoxide and heated in air at 60 °C. Subsequently, an ethanol solution of tetramethylammonium hydroxide pentahydrate was added to the reactor. After stirring the mixture for 1 hour, a precipitate formed and was separated from the reaction mixture using a centrifuge. The precipitate was dispersed in ethanol to obtain Zn 1- x Mg x O nanoparticles (x = 0.15). The resulting nanoparticles were subjected to transmission electron microscopy analysis. The particles had an average size of approximately 3 nm.
[0355] Preparation Example 1:
[0356] In trioctylamine, zinc acetate and ethyl butyrate of the following structure (CAS No. 88 - 09 - 5, Sigma - Aldrich) were each added (at a molar ratio of 1:2 between zinc acetate and ethyl butyrate) and heated under vacuum to 120 °C for 1 hour to prepare the first zinc precursor:
[0357]
[0358] In trioctylamine, zinc acetate and oleic acid of the following structure were each added (at a molar ratio of 1:2 between zinc acetate and oleic acid) and heated under vacuum to 120 °C for 1 hour to prepare the second zinc precursor:
[0359] .
[0360] Trioctylamine was added to a 300 mL reaction flask and heated under vacuum to 120 °C for 1 hour, and nitrogen (N2) was allowed to flow into the flask. When the flask temperature was raised to the reaction temperature (340 °C), an octane dispersion of the particles prepared in the reference example was added, and then the first zinc precursor and dodecanethiol (sulfur precursor) were each injected in two portions.
[0361] After 30 minutes, when the reaction temperature was adjusted to 250 °C to 300 °C, zinc chloride and the second zinc precursor were added. The total reaction time was 70 minutes.
[0362] The molar ratio of the first zinc precursor, the second zinc precursor, and the sulfur precursor (first zinc precursor: second zinc precursor: sulfur precursor) was 2.1:0.4:1.4.
[0363] The molar ratio of the total zinc precursor used to zinc chloride was 2.5:0.4.
[0364] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The obtained semiconductor nanoparticles were dispersed in octane. Photoluminescence spectroscopy and TGA were performed on the obtained semiconductor nanoparticles, and the results are summarized in Table 1.
[0365] GC analysis was performed on the obtained semiconductor nanoparticles, and the results are summarized in Figure 8 . According to Figure 8 the results, a first peak attributed to the ethyl butyrate moiety at a retention time of 6.78 minutes (i.e., the collection time) and a second peak attributed to the oleate moiety at a retention time of 13.13 minutes were each confirmed, and the area percentage of the first peak relative to the area of the second peak (100%) was confirmed to be 62.57%.
[0366] Preparation Example 2:
[0367] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that ethyl hexanoic acid (CAS No. 149-57-5, Sigma-Aldrich) having the following structure was used instead of ethyl butyric acid:
[0368]
[0369] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The obtained semiconductor nanoparticles were dispersed in octane. Photoluminescence spectroscopy and TGA were performed on the obtained semiconductor nanoparticles, and the results are summarized in Table 1. GC analysis was performed on the obtained semiconductor nanoparticles, and the results are summarized in Figure 8 . According to Figure 8 the results, a first peak attributed to the ethyl hexanoate moiety at a retention time of 6.43 minutes and a second peak attributed to the oleate moiety at a retention time of 13.14 minutes were each confirmed, and the area percentage of the first peak relative to the area of the second peak (100%) was confirmed to be 23.53%.
[0370] Preparation Example 3:
[0371] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that propyl valeric acid (CAS No. 99-66-1, Sigma-Aldrich) having the following structure was used instead of ethyl butyric acid:
[0372]
[0373] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The obtained semiconductor nanoparticles were dispersed in octane. Photoluminescence spectroscopy and TGA were performed on the obtained semiconductor nanoparticles, and the results are summarized in Table 1.
[0374] Preparation Example 4:
[0375] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that both ethyl butyrate and ethyl hexanoate were used to prepare the first zinc precursor.
[0376] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The obtained semiconductor nanoparticles were dispersed in octane. Photoluminescence spectroscopy and TGA were performed on the obtained semiconductor nanoparticles, and the results are summarized in Table 1. GC analysis was performed on the obtained semiconductor nanoparticles, and based on the results, the first peak attributed to the ethyl butyrate moiety (peak retention time of 4.42 minutes for EBA attribution) and the ethyl hexanoate moiety (peak retention time of 6.36 minutes for EHA attribution) and the second peak attributed to the oleate moiety (retention time of 13.07 minutes) were confirmed. The area percentage of the first peak (EBA area percentage of 10.7% + EHA area percentage of 32.82%) relative to the area of the second peak (100%) was confirmed to be 43.52%.
[0377] Preparation Example 5:
[0378] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that the amount of zinc chloride used was tripled.
[0379] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The obtained semiconductor nanoparticles were dispersed in octane. It was confirmed that the dispersion of the obtained semiconductor nanoparticles could form a colloidal dispersion. TGA was performed on the obtained semiconductor nanoparticles. As a result, it was confirmed that the organic content was 7.7% by weight, and the residual content at 550 °C was approximately 91.37% by weight.
[0380] Based on the GC analysis of the obtained semiconductor nanoparticles, the first peak attributed to the ethyl hexanoate moiety at a retention time of 6.42 minutes and the second peak attributed to the oleate moiety at a retention time of 13.1 minutes were each confirmed, and the area percentage of the first peak relative to the area of the second peak (100%) was 130%.
[0381] Preparation Example 6:
[0382] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that methyl butyric acid (CAS No. 116-53-0, Sigma-Aldrich) having the following structure was used instead of ethyl butyric acid:
[0383]
[0384] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The resulting semiconductor nanoparticles were dispersed in octane. GC analysis was performed on the resulting semiconductor nanoparticles, and the results are summarized in Figure 8 According to the results of Figure 8 a first peak attributable to the methyl butyrate moiety at a retention time of 3.51 minutes and a second peak attributable to the oleate moiety at a retention time of 13.13 minutes were each confirmed, and the area percentage of the first peak relative to the area of the second peak (100%) was confirmed to be 33.64%.
[0385] TGA was performed on the resulting semiconductor nanoparticles. As a result, the organic content was confirmed to be 10.53 wt%, and the residual content at 550 °C was 87.88 wt%.
[0386] Preparation Example 7:
[0387] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that 2-butyl octanoic acid (CAS No. 27610-92-0, Sigma-Aldrich) having the following structure was used instead of ethyl butyric acid:
[0388]
[0389] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The resulting semiconductor nanoparticles were dispersed in octane. GC analysis was performed on the resulting semiconductor nanoparticles, and the results are summarized in Figure 8 According to the results of Figure 8 a first peak attributable to the 2-butyl octanoate moiety at a retention time of 9.27 minutes and a second peak attributable to the oleate moiety at a retention time of 13.14 minutes were each confirmed, and the area percentage of the first peak relative to the area of the second peak (100%) was confirmed to be 45.95%.
[0390] TGA was performed on the resulting semiconductor nanoparticles. As a result, the organic content was confirmed to be approximately 11.1 wt%, and the residual content at 550 °C was approximately 88 wt%.
[0391] Preparation Comparative Example 1
[0392] Semiconductor nanoparticles were prepared in the same manner as in Preparation Example 1, except that only the second zinc precursor was used without using the first zinc precursor.
[0393] The reactor was cooled to room temperature, and ethanol was added to the reaction solution to promote precipitation of the semiconductor nanoparticles, which were collected by centrifugation. The resulting semiconductor nanoparticles were dispersed in octane. Photoluminescence spectroscopy and TGA were performed on the resulting semiconductor nanoparticles, and the results are summarized in Table 1.
[0394] GC analysis was performed on the resulting semiconductor nanoparticles. From the results, the second peak attributable to the oleate moiety at a retention time of 13.14 minutes was confirmed, but substantially no peak corresponding to the first peak was observed.
[0395] Table 1
[0396]
[0397] PWL: Emission peak wavelength
[0398] FWHM: Full width at half maximum
[0399] Absolute QY: Absolute quantum yield
[0400] Device Example
[0401] Example 1
[0402] Using the semiconductor nanoparticles prepared in Preparation Example 1, an electroluminescent device having the following structure was fabricated: ITO / PEDOT:PSS (300 Å) / TFB (250 Å) / semiconductor nanoparticle emission layer (360 Å) / ZnMgO (240 Å) / Al, and the electroluminescent properties were measured as follows:
[0403] On a glass substrate on which an ITO electrode (first electrode) was deposited, PEDOT:PSS and TFB layers were formed as a hole injection layer and a hole transport layer by spin coating. On the formed TFB layer (25 nm), the semiconductor nanoparticle solution prepared in Preparation Example 1 was spin coated to form an emission layer. On the emission layer, a zinc oxide magnesium nanoparticle layer was formed as an electron assisting layer, and then an Al electrode was deposited to fabricate an electroluminescent device.
[0404] The electroluminescent properties and lifetime of the fabricated device were measured. The electroluminescent properties are summarized in Table 2.
[0405] Example 2
[0406] An electroluminescent device was fabricated in the same manner as in Example 1, except that the semiconductor nanoparticles prepared in Preparation Example 2 were used. The electroluminescent properties and lifetime of the fabricated device were measured. The electroluminescent properties are summarized in Table 2.
[0407] Example 3
[0408] An electroluminescent device was fabricated in the same manner as in Example 1, except that the semiconductor nanoparticles prepared in Preparation Example 3 were used. The lifetime of the fabricated device was measured, and the results are summarized in Table 3.
[0409] Example 4
[0410] An electroluminescent device was fabricated in the same manner as in Example 1, except that the semiconductor nanoparticles prepared in Preparation Example 4 were used. The lifetime of the fabricated device was measured, and the results are summarized in Table 3.
[0411] Example 5
[0412] An electroluminescent device was fabricated in the same manner as in Example 1, except that the semiconductor nanoparticles prepared in Preparation Example 5 were used. The lifetime of the fabricated device was measured, and the results are summarized in Table 4. It was confirmed that the fabricated device had a T90 @ 146 nits greater than 1000 hours.
[0413] Comparative Example 1
[0414] An electroluminescent device was fabricated in the same manner as in Example 1, except that the semiconductor nanoparticles prepared in Comparative Preparation Example 1 were used. The electroluminescent properties and lifetime of the fabricated device were measured, and the results are summarized in Tables 2, 3, and 4.
[0415] Table 2
[0416]
[0417] EQE Max: Maximum external quantum efficiency
[0418] Lum Max: Maximum luminance
[0419] T90 @ 650 nits: T90 (hours) when driven at an initial luminance of 650 nits
[0420] T50 @ 650 nits: T50 (hours) when driven at an initial luminance of 650 nits
[0421] It was confirmed from the results in Table 2 that the electroluminescent device of the example had improved electroluminescent properties and an extended lifetime compared to the device of the comparative example. <q
[0422] Table 3
[0423]
[0424] Relative T90 @ 650 nits: The T90 (hours) of a given device at 650 nits relative to the T90 (hours) of Comparative Example 1 at 650 nits
[0425] Table 4
[0426]
[0427] Relative T90 @ 146 nits: The T90 (hours) of a given device at 146 nits relative to the T90 (hours) of Comparative Example 1 at 146 nits
[0428] It is confirmed from the results in Tables 3 and 4 that the electroluminescent device of the embodiment can have an extended lifespan compared to the device of the comparative example.
[0429] Although the present disclosure has been described in connection with presently considered practical example embodiments, it will be understood that the invention is not limited to the disclosed embodiments, but rather, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. Semiconductor nanoparticles, including: zinc, selenium, and sulfur, and wherein the semiconductor nanoparticles do not include cadmium; wherein the semiconductor nanoparticle comprises a first semiconductor nanocrystal and a semiconductor nanocrystal shell comprising zinc and sulfur disposed on the first semiconductor nanocrystal; wherein the semiconductor nanoparticle further comprises a plurality of organic ligands, the plurality of organic ligands comprising a first organic ligand having a carboxylate moiety and a second organic ligand different from the first organic ligand and having a carboxylate moiety; wherein in gas chromatography analysis, the semiconductor nanoparticles exhibit a first peak attributable to the first organic ligand and a second peak attributable to the second organic ligand; and The area percentage of the first peak relative to the second peak is greater than or equal to 1% and less than or equal to 300%. 2 . The semiconductor nanoparticle according to claim 1 , wherein in a gas chromatography analysis of the semiconductor nanoparticle, a ratio of the retention time of the first peak to the retention time of the second peak is greater than or equal to 0.1:1 and less than 1:
1. 3 . The semiconductor nanoparticle according to claim 1 , wherein an area percentage of the first peak relative to the second peak is greater than or equal to 10% and less than or equal to 140%. The semiconductor nanoparticle according to claim 1 , further comprising chlorine.
5. The semiconductor nanoparticle of claim 1, wherein the semiconductor nanoparticle comprises a Group II-VI compound, a Group III-V compound, a Group IV-VI compound, a Group IV element or compound, a Group II-III-VI compound, a Group I-III-VI compound, a Group I-II-IV-VI compound, or a combination thereof.
6. The semiconductor nanoparticle of claim 1 , wherein the first semiconductor nanocrystal comprises indium phosphide, indium zinc phosphide, zinc selenide, zinc telluride, zinc telluride selenide, silver indium gallium sulfide, silver indium sulfide, or a combination thereof, and The semiconductor nanocrystal shell comprises zinc selenide, zinc selenide telluride, zinc selenide sulfide, zinc sulfide or a combination thereof. The semiconductor nanoparticle according to claim 1 , wherein the total number of carbon atoms in the plurality of organic ligands is greater than or equal to 20 and less than or equal to 34.
8. The semiconductor nanoparticle of claim 1, wherein the first organic ligand has a molecular weight greater than or equal to 90 g / mol and less than or equal to 260 g / mol, The second organic ligand has a molecular weight greater than or equal to 200 g / mol and less than or equal to 500 g / mol.
9. The semiconductor nanoparticle of claim 1 , wherein the first organic ligand comprises a hexanoate moiety substituted by a C1-C3 alkyl group, a butyrate moiety substituted by a C1-C3 alkyl group, a valerate moiety substituted by a C1-C3 alkyl group, an octanoate moiety substituted by a C1-C4 alkyl group, or a combination thereof, and The second organic ligand includes an aliphatic hydrocarbon group having greater than or equal to 17 carbon atoms.
10. The semiconductor nanoparticle of claim 1, wherein the first organic ligand comprises an ethylbutyrate moiety, a 2-ethylhexanoate moiety, a valproate moiety, a methylbutyrate moiety, a butyloctanoate moiety, or a combination thereof, and The second organic ligand comprises an oleate moiety.
11. The semiconductor nanoparticle according to claim 1 , wherein the semiconductor nanoparticle has a weight loss in the range of 200° C. to 550° C. of greater than or equal to 3% and less than or equal to 13% of the total weight of the semiconductor nanoparticle in thermogravimetric analysis, or in, In thermogravimetric analysis, the semiconductor nanoparticles have a residual content at 550° C. of greater than or equal to 87% of a total weight of the semiconductor nanoparticles. 12 . The semiconductor nanoparticle according to claim 1 , wherein a molar ratio of sulfur to selenium in the semiconductor nanoparticle is greater than or equal to 0.4 and less than or equal to 1. 13 . The semiconductor nanoparticle according to claim 1 , further comprising chlorine, and in the semiconductor nanoparticle, a molar ratio of chlorine to zinc is greater than or equal to 0.01 and less than or equal to 1.
14. A method for producing semiconductor nanoparticles according to any one of claims 1 to 13, wherein the method comprises: mixing a zinc precursor with a sulfur precursor in a reaction medium comprising an organic solvent and optionally an organic ligand in the presence of particles comprising first semiconductor nanocrystals and optionally second semiconductor nanocrystals; as well as A metal halide is added to the reaction medium, wherein the zinc precursor includes a first zinc precursor comprising the first organic ligand and zinc ions and a second zinc precursor comprising the second organic ligand and zinc ions.
15. The method of claim 14, wherein the first zinc precursor is a reaction product between a first carboxylic acid compound containing the first organic ligand and a zinc compound, and the second zinc precursor is a reaction product between a second carboxylic acid compound containing the second organic ligand and a zinc compound, wherein the first carboxylic acid compound has an acid dissociation constant greater than or equal to 4.7 and less than or equal to 9, and the second carboxylic acid compound has an acid dissociation constant greater than or equal to 9.2 and less than or equal to 10.
2.
16. The method of claim 14, wherein the metal halide is added to the reaction medium after mixing the first zinc precursor or the second zinc precursor with the sulfur precursor. 17 . The method according to claim 14 , wherein the amount of the second zinc precursor is greater than or equal to 0.1 mole and less than or equal to 10 moles per mole of the first zinc precursor. 18 . The method according to claim 14 , wherein the amount of the metal halide is greater than or equal to 0.05 mole and less than or equal to 0.9 mole per one mole of the zinc precursor.
19. An electroluminescent device comprising a first electrode and a second electrode spaced apart from each other, and a light-emitting layer disposed between the first electrode and the second electrode, wherein the light-emitting layer comprises the semiconductor nanoparticles according to any one of claims 1 to 13.
20. A display device comprising the electroluminescent device according to claim 19.
Citation Information
Patent Citations
Brake for hay wagons
CA116530A
Printing machine
CA149575A
Electronic device and method for displaying image based on interaction
KR1020240016847A